Adolescents' protection motivation and smoking behaviour - Thrul, Johannes Erich; Stemmler, Mark; Bühler, Anneke; Kuntsche, Emmanuel (Health education research, 2013)
The protection motivation theory (PMT) is a well-known theory of behaviour change. This study tested the applicability of the sub-constructs of threat and coping appraisal in predicting adolescents' smoking-related behavioural intentions and smoking behaviour longitudinally. Adolescents (N = 494) aged 11-16 years and not currently smoking at baseline participated in the study. Predictive validity of PMT constructs was tested in a path analysis model. Self-efficacy significantly predicted behavioural intention at baseline, which significantly predicted behavioural intention at follow-up, which in turn predicted smoking behaviour at follow-up. The effect of self-efficacy on behavioural intention at follow-up was mediated by behavioural intention at baseline and the effect of self-efficacy on smoking behaviour was mediated by behavioural intention at baseline and follow-up. In conclusion, we found support for one part of the PMT, namely for the predictive validity of the coping appraisal construct self-efficacy in predicting adolescents' smoking-related behavioural intention and smoking behaviour. These results fail to support the appropriateness of the PMT's construct threat appraisal in longitudinally predicting adolescents' smoking as well as the applicability of communicating fear and negative information as preventive interventions for this target group.

Aggression - Hildebrand, Anja; Stemmler, Mark (Psychologische Förder- und Interventionsprogramme für das Kindes- und Jugendalter, 2021)

A meta-analysis on the effects of incarceration-based opioid substitution treatment - Boksán, Klara; Dechant, Michael; Weiss, Maren; Hellwig, Almut; Stemmler, Mark (Medicine Science and the Law, 2022)
Opioid substitution treatment (OST) is a common treatment for individuals who use opioids; however, empirical evidence on the effects of OST during incarceration is scarce. Our aim was to conduct a meta-analysis on the effects of incarceration-based OST on substance use, treatment engagement post-release and re-incarceration. Method: We searched for studies on individuals who were incarcerated and treated with OST, compared to a comparison group. Studies were only included if they reported data post-release. Results: N = 15 studies met the inclusion criteria. We found less opioid use, less other drug use, higher treatment engagement post-release and less re-incarceration among treated individuals compared to the comparison group. Moderator analyses showed some influence of length of follow-up period and study quality. Conclusions: Incarceration-based OST reduces drug use, re-incarceration and leads to higher treatment engagement after release. More research is needed on the effects of incarceration-based OST n secondary outcomes (e.g. health and social integration) and on factors that moderate these effects.<br
CRIS-Team Scopus Importer:2022-08-19
Keywords: incarcerated populations; meta-analysis; opioid substitution treatment; Opioid use disorder; treatment of incarcerated individuals

Analysis of Categorical Data with the R Package confreq - Heine, Jörg-Henrik; Stemmler, Mark (Psych, 2021)

A nonparametrical evaluation of ANOVA and MANOVA designs using interaction structure analysis - Stemmler, Mark (Biometrical Journal, 1994)
The interaction structure analysis (ISA) is proposed as a nonparametric procedure for the evaluation of uni- and multivariate analysis of variance models. Main effects and interactions of (independent) treatment variables are replaced by interaction-types where types are defined as those treatment-response combinations which occur significantly more often than expected under a null hypothesis (Ho) of no treatment effects. The application of ISA and the typological interpretation of ISA results are illustrated for an ANOVA design from toxicology and for a MANOVA design from psychopharmacology.
Keywords: Nonparametric testing; ANOVA designs; MANOVA designs; Interaction analysis; Treatment response patterns; Configural frequency analysis; Contingency tables; Fourfold tests

Anonymous online cognitive behavioral therapy for sleep disorders in shift workers—a study protocol for a randomized controlled trial - Retzer, Lukas; Feil, Monika; Reindl, Richard; Richter, Kneginja; Lehmann, Robert; Stemmler, Mark; Graessel, Elmar (Trials, 2021)
Background: Many shift workers suffer from sleep issues, which negatively affect quality of life and performance. Scientifically evaluated, structured programs for prevention and treatment are scarce. We developed an anonymous online cognitive behavioral therapy for insomnia (CBT-I) program. After successful completion of a feasibility study, we now start this prospective, randomized, controlled superiority trial to compare outcomes of two parallel groups, namely an intervention group and a waiting-list control-group. Additionally, we will compare these outcomes to those of a face-to-face CBT-I outpatient sample. Methods: Collaborating companies will offer our anonymous online intervention to their shift-working employees. Company physicians and counseling services will screen those interested for inclusion and exclusion criteria. Participants will receive access to our online service, where they will complete psychometric assessment and receive random assignment to either the intervention group or the waiting-list control group. Participants and providers will be aware of the group assignment. We aim to allocate at least N = 60 participants to the trial. The intervention consists of psychoeducation, sleep restriction, stimulus control, relaxation techniques, and individual feedback delivered via four e-mail contacts. During the intervention, as well as during the waiting period, participants will fill out weekly sleep diaries. Immediately after completion of the program, the post-intervention assessment takes place. Participants in the control group will be able to participate in the program after all study assessments. To recruit an additional sample, collaborating outpatient sleep clinics will provide six sessions of standard face-to-face CBT-I to an ad hoc sample of shift working patients. We expect both the online and the face-to-face CBT-I interventions to have beneficial effects compared to the control group on the following primary outcomes: self-reported symptoms of depression and insomnia, sleep quality, and daytime sleepiness. Conclusions: The online intervention allows shift workers to follow a CBT-I program independently of their working schedule and location. Forthcoming results might contribute to further improvement of prevention and therapy of sleep issues in shift workers. Trial registration: German Clinical Trials Register DRKS DRKS00017777. Registered on 14 January 2020—retrospectively registered.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Circadian rhythm sleep disorder; Cognitive behavioral therapy; E-Health; Insomnia; Intervention studies; Shift work; Study protocol

Antisocial behavior and crime: contributions of developmental and evaluation research to prevention and intervention - Bliesener, Thomas; Beelmann, Andreas; Stemmler, Mark (Hogrefe, 2012)

Antisocial Behaviour and Violent Delinquency Among Boys with a Migration Background: A German Panel Study - Uysal, Burcu; Stemmler, Mark; Weiss, Maren (International Journal of Developmental Science, 2020)

App-based maintenance treatment for alcohol use disorder after acute inpatient treatment: Study protocol for a multicentre randomized controlled trial - Saur, Sebastian; Weisel, Kiona; Lang, Catharina; Fuhrmann, Lukas; Steins-Loeber, Sabine; Enewoldsen, Niklas; Reichl, Daniela; Zink, Mathias; Jakobi, Fabian; Rudolph, Melanie; Ahnert, Andreas; Braunwarth, Wolf Dietrich; et al. (Internet Interventions, 2022)
Background: Alcohol use disorder, a prevalent and disabling mental health problem, is often characterized by a chronic disease course. While effective inpatient and aftercare treatment options exist, the transferal of treatment success into everyday life is challenging and many patients remain without further assistance. App-based interventions with human guidance have great potential to support individuals after inpatient treatment, yet evidence on their efficacy remains scarce. Objectives: To develop an app-based intervention with human guidance and evaluate its usability, efficacy, and cost-effectiveness. Methods: Individuals with alcohol use disorder (DSM-5), aged 18 or higher, without history of schizophrenia, undergoing inpatient alcohol use disorder treatment (N = 356) were recruited in eight medical centres in Bavaria, Germany, between December 2019 and August 2021. Participants were randomized in a 1:1 ratio to either receive access to treatment as usual plus an app-based intervention with human guidance (intervention group) or access to treatment as usual plus app-based intervention after the active study phase (waitlist control/TAU group). Telephone-based assessments are conducted by diagnostic interviewers three and six weeks as well as three and six months after randomization. The primary outcome is the relapse risk during the six months after randomization assessed via the Timeline Follow-Back Interview. Secondary outcomes include intervention usage, uptake of aftercare treatments, AUD-related psychopathology, general psychopathology, and quality of life. Discussion: This study will provide further insights into the use of app-based interventions with human guidance as maintenance treatment in individuals with AUD. If shown to be efficacious, the intervention may improve AUD treatment by assisting individuals in maintaining inpatient treatment success after returning into their home setting. Due to the ubiquitous use of smartphones, the intervention has the potential to become part of routine AUD care in Germany and countries with similar healthcare systems.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Alcohol use disorder; App-based intervention; Germany; Human guidance; Maintenance treatment; RCT

Approach and avoidant coping: Implications for adolescent mental health - Herman-Stahl, Mindy A.; Stemmler, Mark; Petersen, Anne C. (Journal of Youth and Adolescence, 1995)
Conducted a short-term longitudinal study examining the structure of coping behavior and the relationship between coping style and depression during adolescence. 603 adolescents in Grades 6–11 were surveyed in the fall of 1989 and again in the fall of 1990. A 2-dimensional model of coping was found using confirmatory factor analysis, with the factors being approach coping and avoidant coping. Approach copers reported the fewest symptoms of depression, while avoidant copers reported the most. Girls used more approach coping than did boys in all grades. Ss who changed over time from approach to avoidant coping evidenced a significant increase in depressive symptoms, whereas Ss who switched from avoidant to approach coping displayed a significant decrease in depression over 1 yr.
Keywords: Coping Behavior; Major Depression; Longitudinal Studies

Are you in or out? Recruitment of adolescent smokers into a behavioral smoking cessation intervention - Thrul, Johannes Erich; Stemmler, Mark; Goecke, Michaela; Bühler, Anneke (Addictive Behaviors, 2015)
INTRODUCTION: Even though many adolescent smokers want to quit, it is difficult to recruit them into smoking cessation interventions. Little is known about which adolescent smokers are currently reached by these measures. In this study we compare participants of a group-based, cognitive behavioral smoking cessation intervention with adolescent smokers who decided against participating. METHODS: Within a non-randomized controlled trial, data of 1053 smokers (aged 11-19) from 42 German secondary schools were analyzed. Of these smokers, 272 were recruited into 47 courses of the intervention. An in-class information session, individually addressing potential participants, and incentives were used as means of recruitment. Personal predictors of participation were analyzed using regression analyses and multivariate path analyses to test for mediation. RESULTS: In the path analysis model, nicotine dependence, quit motivation, and a previous quit attempt were directly positively related to participation. Heavier smoking behavior was indirectly positively associated with participation through nicotine dependence and negatively through quit motivation, yielding an overall positive indirect effect. The positive effect of a previous quit attempt on participation was partially mediated through nicotine dependence and quit motivation. The proportion of smoking friends were indirectly positively related to participation, mediated through nicotine dependence. CONCLUSIONS: Since adolescents with heavier smoking behavior and stronger nicotine dependence are less likely to undertake a successful unassisted quit attempt, the reach of these young smokers with professional cessation interventions is desirable. Further measures to improve the recruitment of those currently not motivated to quit have to be examined in future studies.
Keywords: Behavioral; Cessation; Recruitment; Treatment and intervention; Youth tobacco use

Assessing behavioral changes in antidementia therapy: Perspectives of an international ADL-Project - Erzigkeit, Helmut; Overall, John E.; Stemmler, Mark; Steinwachs, Klaus; Lehfeld, Hartmut; Hulla, Franz (Aging, Health, and Healing, 1995)

A variational approach to Continuous Time Dynamic Models - Meinlschmidt, Hannes; Sons, Meike; Stemmler, Mark (Dependent Data in Social Sciences Research - Forms, Issues and Methods of Analysis (second edition), 2024)

Behandlung opioidabhängiger Inhaftierter – Einstellungen und Behandlungspraxis des medizinischen Personals in bayerischen Justizvollzugsanstalten - Weiss, Maren; Geißelsöder, Kerstin; Breuer, Maike Miriam; Dechant, Michael; Endres, Johann; Stemmler, Mark; Wodarz, Norbert (Gesundheitswesen, 2021)
Background The present study examines the treatment practice and attitudes of medical staff towards opioid-dependent inmates in Bavarian prisons. Method We interviewed medical staff (n=20) from 18 Bavarian prisons about substitution practice and attitudes by semi-structured interviews. Results With regard to the treatment routines and the attitudes of the medical staff, we found mixed results. From the perspective of the medical staff, the treatment decision depends on the patients’ wishes, the severity and duration of the dependence, the length of sentence and organizational factors. Problems were discussed in particular with regard to the care situation inside and outside the prisons and difficulties in transition management. Conclusions Substitution therapy is considered a standard treatment method in prisons today. However, our respondents highlighted some disadvantages (e. g. passing on the substitution drug). Although the treatment goal of complete abstinence was generally viewed positively by a part of the medical staff, it was not considered very realistic. From the point of view of the respondents, special attention should be paid to the continuity of the chosen treatment strategy in the context of discharge management.<br
Keywords: prison; opiate substitution treatment; treatment routines; indication for opioid substitution

Behavioral areas of change under medical treatment - Steinwachs, Klaus; Stemmler, Mark (Aging, Health and Healing, 1995)

Beurteilung von sozialen Verhaltensproblemen und Erziehungsschwierigkeiten im Vorschulalter - Beelmann, Andreas; Lösel, Friedrich; Stemmler, Mark; Jaursch, Stefanie (Diagnostica, 2006)
Der Artikel beschreibt die psychometrische Überprüfung der deutschen Version des Eyberg Child Behavior Inventory (ECBI) an einer Stichprobe von 718 Vorschulkindern mit Angaben von 715 Müttern und 566 Vätern. Die Itemanalyse ergab eine große Bandbreite von mittleren Intensitäts- und Problemratings sowie überwiegend zufriedenstellende Trennschärfen und Interkorrelationen der 36 ECBI-Items. Die Überprüfung der ECBI-Skalen erbrachte gute und mit der US- amerikanischen Standardisierung vergleichbare Reliabilitäten (z. B. Cronbachs D .90). Dagegen zeigten sich zum Teil deutlich höhere Intensitäts- und Problemwerte in unserer deutschen Stichprobe, was auf kulturspezifische Antwortmuster hindeutet. Es bestätigte sich jedoch das Ergebnis, dass Mütter im Vergleich zu Vätern von höheren Problemraten berichteten und Jungen im Vergleich zu Mädchen fast durchgängig höhere Belastungswerte aufwiesen. Die Daten zur Validierung des Verfahren anhand des Social Behavior Questionnaire (SBQ) erbrachten innerhalb des gleichen Informanten substanzielle Zusammenhänge, aber nur geringe Korrelationen zwischen den Angaben unterschiedlicher Informanten (Eltern und Erzieherinnen). Insgesamt erwies sich die deutsche Version des ECBI als ein ökonomisches und sensitives Screening-Verfahren zur Beurteilung von sozialen Verhaltensproblemen bei Vorschulkindern und Erziehungsproblemen der Eltern, das sowohl in pädagogisch-psychologischen als auch klinisch-psychologischen Kontexten eingesetzt werden kann.
Keywords: Diagnostik; Verhaltensstörungen; Vorschulkinder; Dissozialität

Bipredictive configural frequency analysis of small sample MANOVA designs - Müller, Matthias J.; Stemmler, Mark (Psychologische Beiträge, 2000)
Suggests and demonstrates an exact version of bipredictive Configural Frequency Analysis (CFA) for use in multivariate analysis of variance (MANOVA) designs with small samples. In 2 dimensional contingency tables bipredictive CFA is based on Kimball's (1954) chi-square decomposition. The sample used was from a study of acoustic vigilance experiment on 24 Ss in Germany (H. F. L. Meyer-Bahlburg, 1970). The authors emphasize that the application of Kimball's asymptotic chi-square decomposition is more applicable to larger samples.

Brainspotting – the efficacy of a new therapy approach for the treatment of Posttraumatic Stress Disorder in comparison to Eye Movement Desensitization and Reprocessing - Hildebrand, Anja; Grand, David; Stemmler, Mark (Mediterranean Journal of Clinical Psychology, 2017)
Keywords: Evaluation; Posttraumatic Stress Disorder

Change in Juvenile Offending Versatility Predicted by Individual, Familial, and Environmental Risks - Wallner, Susanne; Thomas, Hoben; Stemmler, Mark (International journal of conflict and violence, 2021)
Developmental and life-course criminology elucidate the developmental course and change of antisociality over time, considering that longitudinal trajectories differ. Specific relations between risks and different antisociality outcomes are emphasized. We assume that adolescents have different longitudinal trajectories considering the change of offending over time and that risks contribute variably to offending pathways. The current study is based on a German research project in which adolescents (N = 577) were interviewed in two German cities. Based on self-reported crime data, we utilized the slope values of offending versatility (OV) over time as outcome values in regression mixture models capturing the trends for participants over age and exhibiting two components of offending adolescents. We explored the contribution of different risks to OV, defining specific risk patterns: Acceptance of violence and peer delinquency have significant negative effects on the emergence of OV within the group of adolescents with decreasing OV. Acceptance of violence has a significant negative effect, and corporal punishment has a significant positive effect on the emergence of OV within the group of adolescents with increasing or rather stable OV. The results underline the relevance of the violence-related risk factor corporal punishment for the emergence of OV within the last-mentioned group.
CRIS-Team WoS Importer:2021-10-29

Configural Frequency Analysis (CFA) and other non-parametrical statistical methods: Introduction to Special Topic (Part I) - Stemmler, Mark; von Eye, Alexander (Psychological Test and Assessment Modeling, 2012)

Configural Frequency Analysis (CFA) and other non-parametrical statistical methods: Introduction to Special Topic (Part II) - Stemmler, Mark; von Eye, Alexander (Psychological Test and Assessment Modeling, 2012)

Configural frequency analysis of dependent samples for intra-patient treatment comparisons - Stemmler, Mark; Hammond, Sean (Studia Psychologica, 1997)
The dependent sample Configural Frequency Analysis (CFA; cf. A. von Eye, 1990) a nonparametrical test, is suggested as an alternative to the parametrical t-test for dependent samples. The dependent sample CFA may be used, for example, for detecting intra-patient treatment effects in pre-post or cross-over designs. Contrary to the t-test the dependent sample CFA can be applied to nominal (i.e., binary), ordinal, or continuous response variables. Furthermore, the proposed test may be generalized to two and more response variables. Significant test results or identified cells may be interpreted as discrimination types. Discrimination types are patterns of discrete or polychotomous response variables which contain frequencies occurring more often than expected under a null hypothesis of no treatment effects. The test for discrimination types follows the rationale of the W. Lehmacher (1980) simultaneous sign test which compares row with column marginals in a square contingency table. The dependent sample CFA is illustrated using examples from pharmacological research.
Keywords: Dependent Variables; Experimental Design; Measurement; Treatment

Continuity and patterns of externalizing and internalizing behavior problems in girls: A variable- and person-oriented study from preschool to youth age - Lösel, Friedrich; Stemmler, Mark (Psychological Test and Assessment Modeling, 2012)

Cross-cultural applicability of the Inventory of Problems–29 (IOP–29): a pre-registered German replication of Akca, Tepedelen, et al. (2023) - Höpfner, Henrike; Uysal, Burcu; Stemmler, Mark; Akca, Ali Y.E.; Giromini, Luciano (Psychiatry Psychology and Law, 2025)
Assessing the credibility of psychological problems in forensic evaluations is crucial. The Inventory of Problems–29 (IOP–29) is becoming a valuable symptom validity test (SVT) worldwide and has been validated in over 15 languages. This study evaluates the German IOP–29 and fills a gap by replicating a study of Akca, Tepedelen, et al. We analysed 384 IOP–29 protocols from 128 German-speaking adults (range = 18–87 years) under three conditions: honest, random and feigned responses (post-traumatic stress disorder, PTSD; depression; schizophrenia). Statistical analyses showed that the False Disorder Probability Score (FDS) effectively discriminated between honest and feigned responses (Hedges g = 3.90), with a sensitivity of.91 and a specificity of.95 at an FDS cut-off value of ≥.50. A new index for detecting careless or random responses also showed promising results. This study confirms the utility of the IOP–29 in the German-speaking population and supports its cross-cultural applicability.
CRIS-Team Scopus Importer:2025-01-31
Keywords: depression; feigning; German; IOP–29; malingering; PTSD; schizophrenia; symptom validity test

Cross-Validation of the Newly-Normed SKT for the Detection of MCI and Dementia - Hessler, Johannes Balthasar; Stemmler, Mark; Bickel, Horst (GeroPsych, 2016)

Das Bundesprogramm "Elternchance ist Kinderchance". Zentrale Befunde der Evaluation - Gerleigner, Susanne; Guglhör-Rudan, Angelika; Hein, Kerstin; Müller, Dagmar; Walper, Sabine; Beck, Mira; Schwaß, Mariann; Stemmler, Mark (2014)
Die Kurzbroschüre "Das Bundesprogramm 'Elternchance ist Kinderchance' - Zentrale Befunde der Evaluation" vermittelt einen Überblick über die Erkenntnisse der Begleitforschung zu "Elternchance ist Kinderchance". Das Deutsche Jugendinstitut und die Friedrich-Alexander-Universität Erlangen-Nürnberg haben programm- und prozessbegleitend erhoben, wie sich die teilehmenden Fachkräfte Wissen und Kompetenzen zur Elternbegleitung aneignen und wie durch die veränderte Zusammenarbeit mit Eltern deren Erziehungskompetenzen und Bildung in den Familien gefördert werden. Weitere, detaillierte Ergebnisse werden im wissenschaftlichen Abschlussbericht des Evaluationsteams zum Bundesprogramm "Elternchance ist Kinderchance" zu finden sein.

Das Cracow Risk Assessment Instrument zur Prognose von Dissozialität. Die deutsche Fassung der kanadischen Originalversion von Corrado et al. - Lösel, Friedrich; Wallner, Susanne; Jaursch, Stefanie; Stemmler, Mark (2007)

Das Eltern-Belastungs-Inventar (EBI) Einsatz und Nutzen in der Kinder- und Jugendpsychiatrie und –psychotherapie - Irlbauer-Müller, Viktoria; Eichler, Anna; Donhauser, Johanna; Poehlmann, Nina E.; Stemmler, Mark; Moll, G.H.; Kratz, Oliver (Diagnostica, 2017)
Keywords: Elterliche Belastung; psychisch/verhaltensauffällige Kinder/Jugendliche; KJP; Diagnostik; Behandlung

Das Präventionsprogramm EFEEKT (1. Teil): Entwicklungsförderung in Familien: Eltern- und Kinder-Training - Lösel, Friedrich; Runkel, Daniela; Beelmann, Andreas; Jaursch, Stefanie; Stemmler, Mark (Forum Kriminalprävention, 2010)
Gewalt und Kriminalität junger Menschen sind in vielen Ländern sehr aktuelle Probleme. Dies wird einerseits durch die mediale Berichterstattung über besonders gravierende Einzelfälle gefördert. Andererseits geben auch die weniger spektakulären Verhaltensprobleme Anlass zur Besorgnis. Schwerwiegende Störungen des Sozialverhaltens treten bei etwa 10 % der Kinder und Jugendlichen auf. Darüber hinaus weisen viele zumindest leichtere temporäre Störungen auf. In ihren schweren, früh beginnenden und oft relativ dauerhaften Formen führt die Dissozialität nicht nur zu viel Leid bei den Opfern, Familien und dem weiteren sozialen Umfeld, sondern auch zu erheblichen gesellschaftlichen Kosten. Diese können pro Fall durchaus in die Millionenhöhe führen.

Das Präventionsprogramm EFFEKT (2. Teil): Ausblick und Weiterentwicklung - Lösel, Friedrich; Runkel, Daniela; Beelmann, Andreas; Jaursch, Stefanie; Stemmler, Mark (Forum Kriminalprävention, 2010)
In Teil 1 (fk 1/2010) wurden Ziele, Elemente und Maßnahmen des Präventionsprogramms sowie die Evaluationsergebnisse/differenzielle Effekte vorgestellt. Teil 2 gibt einen Ausblick auf die Weiterentwicklung des Programms. 5. Ausblick und Weiterentwicklungen von EFFEKT Die Ergebnisse der Prozessevaluierung sprechen für eine gelungene Implementierung von EFFEKT. Hinsichtlich der Wirkungsevaluation konnten sowohl für das Kinder- als auch das Elterntraining signifikante Effekte im kindlichen Sozialverhalten nachgewiesen werden. In hier nicht dargestellten Auswertungen fanden wir auch Auswirkungen auf theoretisch vermittelnde Merkmale, zum Beispiel auf die soziale Informationsverarbeitung beim Kindertraining und das Erziehungsverhalten beim Elterntraining.

Das Präventionsprogramm Entwicklungsförderung in Familien: Eltern- und Kinder-Training (EFFEKT) - Lösel, Friedrich; Runkel, Daniela; Beelmann, Andreas; Jaursch, Stefanie; Stemmler, Mark (Theorie und Praxis gesellschaftlichen Zusammenhalts, 2008)

Delinquentes Verhalten Jugendlicher im Selbstbericht: Worin unterscheiden sich Täter von Nichttätern? - Wallner, Susanne; Stemmler, Mark (15. Tagung der Fachgruppe Rechtspsychologie der Deutschen Gesellschaft für Psychologie (DGPs), 2013)

Demenzdiagnostik - Stemmler, Mark; Kornhuber, Johannes (Hogrefe, 2018)

Dependent Data in Social Sciences Research - Forms, Issues, and Methods of Analysis - Stemmler, Mark; von Eye, Alexander; Wiedermann, Wolfgang (Springer, 2015)

Dependent Data in Social Sciences Research - Forms, Issues, and Methods of Analysis - Stemmler, Mark; Wiedermann, Wolfgang; Huang, Francis (Springer Verlag, 2024)
All authors of this volume are leading experts in their field of applying or developing new statistical methods for dependent data scenarios. This second edition is again truly international, with authors from the US, Europe and Asia. The book consists of 29 chapters and seven sections. Therefore, the new second edition can be considered a compendium on the up-to-date and cutting edge methods in the field. The seven sections are: (1) growth curve modeling, continuous time modeling and dynamic modeling, (2) network analysis and causal structure learning, (3) multilevel analysis, (4) longitudinal and cross-sectional dependent categorical data analysis and discrete sequence analysis, (5) longitudinal modeling and estimation of missing data, (6) item-response-modeling for dependent data and (7) other methods for the analysis of dependent data.<br

Depression in Adolescence - Petersen, Anne C.; Compas, Bruce E.; Brooks-Gunn, Jeanne; Stemmler, Mark; Ey, Sydney; Grant, Kathryn E. (American Psychologist, 1993)
Adolescence is an important developmental period for understanding the nature, course, and treatment of depression. Recent research concerned with depressive mood, syndromes, and disorders during adolescence is reviewed, including investigations of the prevalence, course, risk factors, and prevention and treatment programs for each of these 3 levels of depressive phenomena in adolescence. A broad biopsychosocial perspective on adolescent depression is recommended, and possible directions for future integrative research are proposed. Based on current research and knowledge, implications for research, program, and national policy are considered.
Keywords: Major Depression; At Risk Populations; Disease Course; Treatment

Depressive symptoms and delinquency as predictors of substance use in young adulthood - Wallner, Susanne; Stemmler, Mark; Petersen, Anne C. (International Society for the Study of Behavioural Development (ISSBD), 2012)

Der Beitrag von geringer Selbstkontrolle, problematischem Erziehungsverhalten, gewalthaltigen Medien und Peerdevianz zur Vorhersage von Jugenddelinquenz - Sauter, Katharina; Wallner, Susanne; Stemmler, Mark (Rechtspsychologie, 2018)

Developmental pathways of externalizing behavior from preschool age to adolescence: An application of general growth mixture modeling - Stemmler, Mark; Lösel, Friedrich (Dependent Data in Social Sciences Research - Forms, Issues, and Methods of Analysis, 2015)

Devianz und Delinquenz im Kindes- und Jugendalter: Ungleichheitsdimensionen und Risikofaktoren - Reinecke, Jost; Stemmler, Mark; Wittenberg, Jochen (Springer VS, 2016)
Delinquentes Verhalten von Kindern- und Jugendlichen wird im Lichte verschiedener Dimensionen von sozialer Ungleichheit beschrieben. Zum Vergleich wird auch abweichendes Verhalten in die empirische Prüfung der Erklärungsansätze einbezogen. Die Befunde stellen den Beginn einer Analyse dar, die Unterschiede in der Lebenssituation, sowie den Einfluss sozialer Ungleichheit auf die Entstehung und Entwicklung abweichender Lebensläufe in den Blick nimmt. Zu den Ungleichheitsdimensionen zählen hierbei askriptive Aspekte (u.a. Geschlecht, Migrationshintergrund, Nachbarschaften), kulturelle Differenzen (z.B. Freizeitverhalten, Peers, Erziehungsstile) und persönliche Heterogenitäten (Werte, Selbstkontrolle, psychopatische Merkmale). Umfangreiche Erhebungen in Schulklassen aus Dortmund und Nürnberg erlauben überdies auch städtevergleichende Auswertunge
Keywords: Devianz; Delinquenz; Akriptive Ungleichheitsdimensionen; Schulprozesse; Persönliche Heterogenitäten; Kulturelle Differenzen

Devianz und Delinquenz in der Kindheit und Jugend – Neue Ansätze der kriminologischen Forschung - Wallner, Susanne; Weiss, Maren; Reinecke, Jost; Stemmler, Mark (Springer VS, 2019)
<br

Diagnostik und Verlauf von kognitiven Fähigkeiten bei älteren Menschen - Stemmler, Mark; Petermann, Franz; Daseking, Monika; Siebert, Jelena; Schott, Hannah; Lehfeld, Hartmut; Horn, Ralf (Gesundheitswesen, 2013)
Hintergrund: Zu den Standardaufgaben von Ärzten und Ärztinnen in Gesundheitsämtern gehört seit jeher die Entwicklungsdiagnostik von Kindern. Angesichts der zunehmenden Anzahl von dementiellen Erkrankungen in Deutschland rückt eine Entwicklungsdiagnostik im Alter stärker in den Mittelpunkt. Eine solche Diagnostik gibt Auskunft darüber, ob die untersuchte Person sich unauffällig und altersentsprechend entwickelt oder ob die in der Untersuchung erzielten kognitiven Leistungen Hinweise auf einen pathologischen (dementiellen) Prozess geben. Studienziel: Es werden 2 Tests zur Erfassung von kognitiven Leistungen im Alter vorgestellt: die Wechsler Adult Intelligence Scale (WAIS-IV) und der Syndrom-Kurztest (SKT), ein Test zur Erfassung von Gedächtnis- und Aufmerksamkeitsstörungen. Ferner werden Übereinstimmungen und Unterschiede zwischen beiden Verfahren beschrieben. Methode: Im Rahmen einer multizentrischen Studie im deutschsprachigen Raum wurden Daten von 504 kognitiv unauffälligen Probanden im Alter von 60 bis 90 mit der WAIS-IV und dem SKT erhoben und ausgewertet. Ergebnisse und Schlußfolgerung: Die Ergebnisse deuten darauf hin, dass mit zunehmenden Alter sowohl kognitive Leistungen der fluiden als auch der kristallinen Intelligenz signifikant abnehmen. In nur 2 Untertests des WAIS-IV gab es keine signifikanten Mittelwertunterschiede in Abhängigkeit des Alters (Allgemeines Wissen und Mosaik Test). Die SKT-Scores zum Gedächtnis und Aufmerksamkeit korrelierten signifikant mit fast allen Untertestes des WAIS. Am stärksten korrelierten die SKT-Aufmerksamkeitscores mit den Untertests zur Verarbeitungsgeschwindigkeit (VG), Wahrnehmungsgebundenes Logisches Denken (WLD) und Arbeitsgedächtnis (AG). Verantwortlich für den kognitiven Abbau sind in erster Linie Verminderungen in der Verarbeitungsgeschwindigkeit sowie beim Arbeitsgedächtnis.

Die Entwicklung von sozialer Informationsverarbeitung und die Vorhersage physischer Aggression im Vorschulalter - Beelmann, Andreas; Lösel, Friedrich; Stemmler, Mark; Jaursch, Stefanie (Psychologie in Erziehung und Unterricht, 2010)

Die Evaluation des Bundesprogramms „Elternchance ist Kinderchance“ - Walper, Sabine; Stemmler, Mark (Frühe Bildung in der Familie – Perspektiven der Familienbildung, 2013)

Die Konfigurationsfrequenzanalyse: Kieser's Test gegen Victor's Typen und Syndrome - von Eye, Alexander; Stemmler, Mark (Zeitschrift für Klinische Psychologie, Psychopathologie und Psychotherapie, 1992)

Die therapeutische Wirksamkeit von Brainspotting im Vergleich zu EMDR bei der Behandlung von PTBS. - Hildebrand, Anja; Stemmler, Mark (Trauma - Zeitschrift für Psychotraumatologie und ihre Anwendungen, 2017)

Different methodological approaches for the construction of a therapy sensitive ADL scale for the assessment of Alzheimer patients - Stemmler, Mark; Steinwachs, Klaus; Lehfeld, Hartmut; Jentzsch, Juliane; Tritt, Karin; Hulla, Franz; Erzigkeit, Helmut (New Trends in the Diagnosis and Therapy of Alzheimer’s Disease, 1994)
The purpose of this paper was the presentation of the work of the international ADL project which aims to construct a therapy sensitive ADL scale for cognitively impaired elderly or demented patients. No final scale was presented, rather different ways for generating ADL items were introduced. Different methodological approaches were applied because no existing ADL or I ADL scale meets the various goals of the international ADL project. By surveying existing scales or assessment tools for measuring daily life behaviour it was recognized that no traditional method of scale construction seems appropriate. Instead, different methodological approaches were adapted in order to meet the high demands for a newly to be constructed internationally valid and therapy sensitive ADL scale for mild to moderate dementia. The scale construction is still in progress. A first scale is expected to be tested by the end of 1994. An international validation in European and American research centers (including one center in Russia) is planne

Different Pathways of Externalising Behaviour Problems From Preschool to Youth: A Test of Risk and Protective Factors and Potential Origins - Lösel, Friedrich; Stemmler, Mark; Bender, Doris (Criminal behaviour and mental health, 2025)
Background: This article is dedicated to David Farrington who was a giant in criminology and, in particular, a pioneer in studying developmental pathways of delinquent and antisocial behaviour. Numerous studies followed his work. Systematic reviews of his and others' research described between two and seven (mainly 3–5) trajectories. The variation is due to the age of individuals, kind and seriousness of problem behaviour, data sources, assessment methods and cultural context. Reviews stated a lack of research on very early starting problem behaviour, broad developmental outcomes, data from multiple informants and (beyond description) on risk and protective factors or potential causes of the different trajectories. Aims: The present study addresses these issues in a prospective longitudinal design and test of the concept of antisocial potential (AP) in Farrington's ICAP theory. Methods: Data on more than 600 children and their families were gathered in a prospective longitudinal design over 10 years in Germany. To avoid potentially negative effects of criminal justice interventions, the study concentrates on child development from ages 4–5 to 6–7, 8–9, 10–12 and 13–14 years. Child externalising behaviour problems were assessed using the social behaviour questionnaire by kindergarten educators, mothers, school teachers and youth self-reports. Developmental trajectories were analysed by general growth curve modelling (GGCM) across five time points. The prediction and explanation of different pathways included family factors (SES, stressful life events, aggressive and inconsistent parenting) and child characteristics (intelligence, resting heart rate, disruptive behaviour, temperament and social adaptability). In accordance with dose–response relationships, we also tested accumulated factors in the Cracow Risk/Needs Instrument. Results: The GGCM analysis revealed five developmental trajectories: high-chronics (2.4%), high-reducers (7.9%), medium-reducers (22.4%), late-starters medium (8.7%) and low-chronics (continuously unproblematic youngsters; 58.6%). Although the group with high externalising problems across all time points was rather small due to the affluent context of the region, there were significant social and individual differences between this and the other groups that fitted to ICAP theory. Furthermore, the study revealed differences between those youngsters that desisted from behaviour problems or started later. The predictive validity of accumulated factors in the Cracow Risk/Needs Instrument was very good for the comparison of the groups with persistently high versus no serious behaviour problems. Conclusions: Our results showed that different pathways of aggressive, delinquent, impulsive and other externalising behaviour already commence in early childhood. Behavioural stability (high- vs. low-chronic problems) was well predicted by child and family characteristics, but there were also plausible findings on trajectories of behavioural change. Overall, the findings underline the need for early developmental prevention.
CRIS-Team Scopus Importer:2025-01-31

Different patterns of boys' externalizing behaviour and their relation to risk factors: A longitudinal study of preschool children - Stemmler, Mark; Lösel, Friedrich (Bulletin de la Société des Sciences Médicales du Grand-Duché de Luxembourg, 2010)
Childrens' externalizing behaviors such as aggression, delinquency and impulsivity are serious problems in many societies. In previous person-oriented analyses we found two types of externalizing problems in boys. One pattern contained externalizing problems only, whereas the other type showed both externalizing and internalizing problems (anxiety, depression etc.). The present study addressed these two groups in a prospective longitudinal design. It was investigated whether the previous descriptive findings remained stable over time and, in particular, whether the two types differed in important risk factors for antisocial behavior. The sample consisted of 198 boys from the Erlangen-Nuremberg Development and Prevention Study. The first assessment took place in kindergarten and the second 3.4 years later in elementary school. The behavior problems were assessed by ratings of kindergarten teachers and elementary school teachers using the Social Behavior Questionnaire (SBQ). The risk factors were low socio-economic status of the family, birth complications, physical punishment in parenting behavior, difficult temperament, low intelligence, and aggression-prone social information processing of the child. Approximately 15% of the boys revealed externalizing behavior problems. A variable-oriented analysis showed significant stability over time. In a person-oriented Configural Frequency Analysis the 'externalizing only' and the 'combined externalizing and internalizing' pattern could be replicated. For five of the six risk factors we found significant differences between the boys with behavior problems and a non-deviant group. However, the two different patterns of externalizing problems differed only in intelligence (lower for the group with combined problems). The results confirm models of cumulative biological, psychological and social risks for antisocial behavior over time. Furthermore, specified analyses of the two types and their relation to proactive and reactive aggression are recommended.

Diskrepanzen zwischen Selbst- und Lehrkräfteurteil bei der Einschätzung antisozialen Verhaltens im Kindesalter - Eine Untersuchung individueller und kontextbezogener Einflussgrößen - Link, Eva; Weiss, Maren; Arnis, Maria; Stemmler, Mark (Psychologie in Erziehung und Unterricht, 2018)
Keywords: Lesemotivation; intrinsische Motivation; extrinsische Motivation; Lesefähigkeit; Textverstehen

Duration of lithium treatment and brain lithium concentration in patients with unipolar and schizoaffective disorder: A study with magnetic resonance spectroscopy - Riedl, Ulrich; Barocka, Arnd; Kolem, Heinrich; Demling, Joachim; Kaschka, Wolfgang P.; Schelp, Rainer; Stemmler, Mark; Ebert, Dieter (Biological Psychiatry, 1997)
Twenty psychiatric patients on lithium medication were examined with 7-Li-magnetic resonance spectroscopy of the brain. Patients on long-term lithium treatment (>6 months) were compared with a short-term group who had been taking lithium for between 4 and 8 weeks. Patients met DSM-III-R criteria for either recurrent unipolar depressive disorder (DSM-III-R 296.3x) or schizoaffective disorder, depressive type (DSM-III-R 295.70). The brain:serum lithium ratio was 0.76 ± 0.26; there was no significant difference between short-term and long-term treatment. In the group of long-term treatment patients there was a positive correlation between lithium dose per day and brain lithium concentration (R = .72, p <.01), and between lithium plasma concentration and brain lithium concentration (R = .65, p < .05). In the short-term group, however, there was no significant correlation for these parameters. No differences between unipolar and schizoaffective disorder were found.
Keywords: Lithium; magnetic resonance spectroscopy; unipolar disorder; schizoaffective disorder

Dysregulation of the autonomic nervous system in adult attention deficit hyperactivity disorder. A systematic review - Geiss, Lennard; Stemmler, Mark; Beck, Beate; Hillemacher, Thomas; Widder, Michael; Hösl, Katharina M. (Cognitive Neuropsychiatry, 2023)
Background: Adult Attention Deficit Hyperactivity Disorder (aADHD) is characterised by inattention, hyperactivity, impulsivity, and emotional instability, all of which were linked to altered modulation of the autonomic nervous system. This and the clinical effectiveness of sympathomimetic medication raised the question if autonomic modulation is altered in aADHD patients. Methods: We systematically searched PubMed, Cochrane Library, and Web Of Science for publications investigating autonomic modulation in aADHD and controls during resting-state and/or under task conditions. Results: We reviewed 15 studies involving 846 participants (424 aADHD and 422 controls), including 4 studies on sympathetic tone at rest, 13 studies on sympathetic modulation during tasks, 3 studies on resting state parasympathetic modulation and 3 papers on task-related parasympathetic modulation. Studies comprised measurements of electrodermal activity, heart rate variability, blood pressure variability, blood volume pulse, pre-ejection period, and baroreflex sensitivity. 2 studies reported reduced sympathetic tone in aADHD; 7 papers described lower sympathetic reactivity to task demands in this cohort. One study linked aADHD to impaired vagal tone, while no indications of altered tasks-related parasympathetic reactivity in aADHD patients were reported. Conclusion: The reviewed data revealed impaired cardiovascular autonomic modulation in aADHD patients, predominantly in sympathetic modulation and during stress exposure.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Attention deficit hyperactivity disorder; autonomic nervous system; central autonomic network; heart rate variability; psychophysiology

Effectiveness of a Multimodal, Day Clinic Group-Based Treatment Program for Trauma-Related Disorders: Differential Therapy Outcome for Complex PTSD vs. Non-Complex Trauma-Related Disorders - Philipps, Anke; Silbermann, Andrea; Morawa, Eva; Stemmler, Mark; Erim, Yesim (Frontiers in Psychiatry, 2019)
Background: The effectiveness of the psychotherapeutic treatment of posttraumatic stress disorder is evidence-based and generally considered proven. However, the effectiveness of multimodal, group-based day clinic treatment programs has rarely been investigated. Moreover, there is no consensus in the literature concerning the question whether psychotherapeutic approaches for trauma-related disorders are also applicable for patients with complex PTSD (cPTSD). The aim of the study was to evaluate our multimodal group-based treatment program regarding a change of psychiatric burden, a change of protective factors, and possible differences in therapy outcome for patients with or without cPTSD. Methods: The group-based treatment for patients with trauma-related disorders was examined in 66 patients who filled out the following questionnaires in the first and in the last week of treatment: Essen Trauma Inventory (ETI), Screening for complex PTSD (SkPTBS), Patient Health Questionnaire—somatization module (PHQ-15), Beck Depression Inventory—Revised (BDI-II), Posttraumatic Growth Inventory (PTGI), and Questionnaire on social support (F-SozU). Results: The treatment was shown to significantly reduce depressive symptoms (p < 0.001, d = -0.536) and increase posttraumatic growth (New Possibilities: p = 0.004, d = 0.405; Personal Strength: p = 0.005, d = 0.414). For patients with cPTSD, depressive (p = 0.010, d = -0.63) as well as cPTSD symptoms (p = 0.020, d = -0.796) were significantly reduced; perceived social support was increased after day clinic treatment (p = 0.003, d = 0.61). Contrary to our expectations, somatoform symptoms were increased after therapy. Conclusions: The present work expands previous research by demonstrating that multimodal group-based, day clinic treatment is effective in the treatment of trauma-related disorders, also in their complex form.
CRIS-Team Scopus Importer:2019-12-03
Keywords: complex PTSD; day clinic treatment; depression; posttraumatic growth; posttraumatic stress disorder; social support; therapy outcome; trauma

EFFEKT-E: Wirksamkeit eines Präventionsprogramms für Kinder emotional belasteter Mütter - Bühler, Anneke; Kötter, Charlotte; Stemmler, Mark; Jaursch, Stefanie; Lösel, Friedrich (Gesundheitswesen, 2015)
Projektziel war es, ein wirksames selektives Präventionsprogramm für Kinder depressiver Mütter zu entwickeln. Mittels eines quasiexperimentellen Evaluationsdesigns wurde das auf Basis eines universellen Programms neu entwickelte Mütter- und Kindertraining in 13 Mutter-Kind-Kliniken evaluiert. Es zeigte sich, dass das depressionsspezifische Programm EFFEKT-E seine Zielgruppe erreicht und von ihr akzeptiert wird, sich gut in die Regelleistungen integrieren lässt und kurz- und längerfristige Effekte auf die mütterliche Kompetenz sowie auf emotionale Probleme von Kindern erreicht.
Keywords: selektive Prävention; familienorientiert; Depression; Verhaltensprobleme; Kinder; depressive Mütter

Efficient ways to impute incomplete panel data - Kleinke, Kristian; Stemmler, Mark; Reinecke, Jost; Lösel, Friedrich (Advances in Statistical Analysis, 2011)
We find that existing multiple imputation procedures that are currently im- plemented in major statistical packages and that are available to the wide majority of data analysts are limited with regard to handling incomplete panel data. We review various missing data methods that we deem useful for the analysis of incomplete panel data and discuss, how some of the shortcomings of existing procedures can be overcome. In a simulation study based on real panel data, we illustrate these proce- dures’ quality and outline fruitful avenues of future research.

Eine mikrosoziologisch inspirierte empirische Annäherung an die positive Generalprävention: Panelanalysen aus Deutschland mit gemischten Befunden - Hirtenlehner, Helmut; Reinecke, Jost; Stemmler, Mark (Monatsschrift für Kriminologie und Strafrechtsreform, 2023)
Positive general prevention assumes that observable criminal punishment stabilizes the audience s moral values, which in turn fosters compliance with the law. This harmonizes with a chain of relationships on the individual level according to which people s sanction risk estimates influence their acceptance of legal rules, with the latter facilitating adherence to the law. Despite the significance of the idea of positive general prevention in the jurisprudential discourse, only scant empirical research is dedicated to the issue. Hence, the impact chain outlined above is tested here with panel data from adolescents living in Dortmund or Nuremberg. Lagged path analyses corroborate the hypothesized effect sequence for shoplifting (with weak relationships in the expected direction), but not for physical assault. These findings are interpreted as partially supportive of the notion of positive general prevention. The hypothesis that delinquent friends transmit information about the widespread impunity of criminal behavior and thus attenuate an individual s commitment to the rules of law accords also well with the idea of positive general prevention. Lagged analyses confirm for physical assault, but not for shoplift-ing, that association with delinquent peers erodes young people s personal acceptance of legal norms.
CRIS-Team Scopus Importer:2023-04-14
Keywords: norm acceptance; panel analysis; peer delinquency; positive general prevention

Ein kurzer Leistungstest zur Erfassung von Störungen des Gedächtnisses und der Aufmerksamkeit SKT Manual Edition 2015 – und der regressionsbasierte Ansatz - Stemmler, Mark; Lehfeld, Hartmut; Siebert, Jelena; Horn, Ralf (Diagnostica, 2017)

Elterliche Belastung und die Zuverlässigkeit von Elternangaben in der Diagnostik psychisch und verhaltensauffälliger Kinder und Jugendlicher - Irlbauer-Müller, Viktoria; Eichler, Anna; Stemmler, Mark; Moll, Gunther; Kratz, Oliver (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2016)

Elterntrainings zur Prävention dissozialen Verhaltens: Grundlagen und eigene Beispiele - Jaursch, Stefanie; Lösel, Friedrich; Stemmler, Mark; Beelmann, Andreas (Forensische Psychiatrie, Psychologie, Kriminologie, 2012)
In diesem Beitrag wird das EFFEKT®- (EntwicklungsFörderung in Familien: Eltern- und Kindertraining)Elterntraining vorgestellt. Die im Rahmen der Erlangen-Nürnberger Entwicklungs- und Präventionsstudie (Lösel et al., Möglichkeiten der Gewaltprävention, S 201–249, 2005; Lösel et al., Z Klin Psychol Psychother 35:127–139, 2006) entwickelten und evaluierten realisierten universellen Maßnahmen zur Prävention dissozialen Verhaltens wurden unterdessen um verschiedene Komponenten auf die gezielte Prävention ausgeweitet: Adaptationen für Eltern von Kindern mit Migrationshintergrund, für depressive Mütter sowie für international mobile Familien, für Eltern von Kleinkindern (unter 3 Jahren), Schulkindern sowie von Teenagern. Darüber hinaus wird das Elterntraining europaweit umgesetzt und mithilfe eines virtuellen Netzwerks besonders niederschwellig angeboten. Es werden vornehmlich die Programminhalte und jeweils anschließend einige Evaluationsergebnisse dargestellt. Diese sprechen für eine gelungene Implementierung der EFFEKT®-Elterntrainings. Hinsichtlich der Wirksamkeit zeigte sich, dass die Trainings nachweisbare Effekte auf das Verhalten der Kinder haben. Die Trainingsgruppen schnitten in allen Bereichen besser ab als die Kontrollgruppen. Die Ergebnisse belegen, dass die Maßnahmen sowohl universell als auch selektiv eingesetzt werden können.
Keywords: Prävention dissozialen Verhaltens bei Kindern; Universelle Prävention; Selektive Prävention; Elterntraining; Evaluation

Entstehung devianten und delinquenten Verhaltens im Lebensverlauf: Die Studie „Chancen und Risiken im Lebensverlauf“ im Überblick - Wallner, Susanne; Weiss, Maren; Stemmler, Mark (49. Kongress der Deutschen Gesellschaft für Psychologie (DGPs), 2014)

Entstehung und Entwicklung von Kinder- und Jugenddelinquenz: erste Ergebnisse einer Längsschnittstudie - Reinecke, Jost; Stemmler, Mark; Arnis, Maria; El-Kayed, Nihad; Meinert, Julia; Pöge, Andreas; Schepers, Deborah; Sünkel, Zara; Uysal, Burcu; Wallner, Susanne; Weiss, Maren; Wittenberg, Jochen (Neue Kriminalpolitik, 2013)

Entwicklungsdiagnostik im Alter: Wie kann man unauffällige kognitive Leistungen von pathologischen unterscheiden? - Stemmler, Mark; Horn, Ralf; Lehfeld, Hartmut; Petermann, Franz; Siebert, Jelena (Diagnostica, 2013)
An approach for the developmental psychological assessment of aging which is able to differentiate normal cognitive aging from pathological cognitive decline is presented.Aregression based approach by Zachary and Gorsuch (1985) was adopted. The analyses were based on data from a multi-center study of N=349 cognitively healthy elderly, aged between 60 and 90 years. Subjects were tested with the SKT (Erzigkeit, 1989), a test for the assessment of attention and memory, and two subtests from the German adaptation of the Wechsler Adult Intelligence Scale (WAIS-IV; Petermann, 2012), the matrix reasoning and the vocabulary subtest. Surprisingly, for the matrix reasoning subtest as well as for the vocabulary subtest, a significant cognitive decline depending on age emerged. All cognitive achievements were significantly correlated with attention, and also, but to a lesser degree, with memory. The results of the regression based approach suggested a valuable contribution to the developmental psychological assessment of aging. © 2013 Hogrefe Verlag, Göttingen.
Keywords: regression-based norms; cognitive degeneration; syndrome short test; WAIS-IV (German adaptation); developmental psychological assessment in old age

Entwicklungsförderung in Familien: Eltern- und Kinder-Training (EFFEKT) - Jaursch, Stefanie; Stemmler, Mark; Lösel, Friedrich; Beelmann, Andreas (Erziehung – (k)ein einfaches Geschäft, 2008)

Evaluation des Bundesprogramms "Elternchance ist Kinderchance - Elternbegleitung der Bildungsverläufe der Kinder". Abschlussbericht - Müller, Dagmar; Beck, Mira; Gerleigner, Susanne; Guglhör-Rudan, Angelika; Hein, Kerstin; Schwaß, Mariann; Stemmler, Mark; Walper, Sabine (2015)

Evaluierung [U25]: Ergebnisse zur Wirksamkeit der [U25] Online-Suizidpräventions-Beratung für junge Menschen - Hildebrand, Anja; Weiss, Maren; Braun-Scharm, Hellmuth; Stemmler, Mark (11. Workshopkongress für Klinische Psychologie und Psychotherapie, 2019)

Experiences in Disseminating Evidence-Based Prevention Programs in a Real-World Setting - Frantz, Inga; Stemmler, Mark; Hahlweg, Kurt; Plück, Julia; Heinrichs, Nina (Prevention Science, 2015)
The primary aim of family-based prevention programs is to promote children's health. Unfortunately, it is difficult to reach families with such evidence-based prevention programs (EBP). Therefore, implementing EBP on a population level could be a promising approach to reach more families, including those faced with socioeconomic challenges who are usually less likely to participate in randomized controlled trials (RCT). Is a population rollout appropriate to reach more and different families than those participating in RCT, especially those representative of the target population? We implemented three EBP in a city in an uncontrolled trial. The effects of this population rollout were tracked on the level of the participating families and on the level of all families living in the city. More than 3480 families (30 % of the population) with children up to 12 years of age participated based on practitioner report. Analyses indicate that a greater percentage of low socioeconomic-status families attended a program compared with a randomly surveyed sample from the city's general population. The sizes of the within-subject effect for parental strategies, child behavior problems, and children's quality of life for a subsample of n = 411 families were similar to those of other uncontrolled EBP studies. The study contributes to highly needed type 2 translation research. The population-based dissemination of EBP could be a promising approach to reach families at risk. However, there are considerable barriers to the implementation process, which currently limit the effectiveness of this rollout in a community.
Keywords: Prevention; Dissemination; Implementation; Parenting; Child behavior

Fathers, mothers and family violence: Which risk factors contribute to the occurrence of child maltreatment and exposure to intimate partner violence in early childhood? Findings in a German longitudinal in-depth study - Liel, Christoph; Eickhorst, Andreas; Zimmermann, Peter; Stemmler, Mark; Walper, Sabine (Child Abuse & Neglect, 2022)
Background: Family violence, especially child maltreatment and intimate partner violence, in early childhood has a strong impact on negative developmental outcomes. There is evidence of child, parental, and family risk factors. Less is known about paternal than maternal risk factors. Objective: To identify maternal and paternal predictors of family violence and predictive constellations of risk factors. Participants and setting: According to psychosocial adversity in a larger study, families were stratified into low-, medium- and high-risk groups. Both, mothers and fathers (n = 197/191), were investigated longitudinally across seven months using self-report questionnaires and ratings of the IFEEL Pictures. Methods: χ2-tests, logistic regression models, and prediction configural frequency analysis (P-CFA) were employed. Results: Univariate predictors (p < .05) were anxiety and stress in mothers, and insensitivity in recognizing negative child emotions in fathers. Within high-risk levels, paternal adverse childhood experiences (ACE) were a predictor (z = 2.92, p > .01), proven by P-CFA. Logistic regression models including family violence at baseline, sociodemographic variables, univariate predictors, and ACE of both parents revealed maternal anxiety (OR = 1.22, p < .05) and low paternal recognition of negative IFEEL Pictures (OR = 6.00, p < .05) as predictors. P-CFA identified socioemotional problems in children and low paternal recognition of negative child emotions as a predictive risk constellation (z = 2.58, p > .01). Conclusion: Analysis of both caregivers in small population samples with oversampled at-risk families leads to a systemic perspective of family violence. The identified risk constellation is highly relevant for early childhood intervention.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Fathers; Mothers; Early childhood; Risk factors; Child maltreatment; intimate partner violence

Flow-Experience in Old Age: An Investigation of Influencing Factors and Therapy Benefits for Geriatric Patients - Wunner, Christina; Hesel, Julia; Stemmler, Mark; Gosch, Markus; Waller, Christiane (Psychotherapie Psychosomatik Medizinische Psychologie, 2022)
Flow experience, a feeling of being absorbed in an activity without reflection and with maximum depth, has positive effects on psychological and physical well-being, performance, and life satisfaction. Little research has been done on flow experience in old age, and there are no studies on geriatric patients. In the present study, elderly patients (mean age:81.2, SD=5.9) of a day hospital were examined with regard to their flow experience using the flow short scale. In addition to age and gender effects, flow was assessed during two different activities ( physical activity vs. memory training). Furthermore, the role of individual activity and group dynamics as well as correlations between flow and therapy success were examined in detail. The results show that flow experience is possible even in old age. Depressed patients experienced as much flow as non-depressed patients; cognitively impaired patients, on the other hand, experienced less flow than patients without cognitive deficits, and chronic pain patients even reported more flow experiences during exercise programs than patients without pain. A high level of self-activity had an overall positive effect on the flow experience. The therapy outcome could not be influenced by flow. Flow experience in old age should be given more attention, especially in physical activity therapy for pain patients; further correlations, especially with regard to depression, remain to be investigated.
CRIS-Team WoS Importer:2022-02-04

Förderung begrifflich-kategorialer Verarbeitung - Grünke, Matthias; Stemmler, Mark (Interventionen bei Lernstörungen: Förderung, Training und Therapie in der Praxis, 2014)

Förderung bei externalisierenden Problemen: Aggression - Stemmler, Mark; Hacker, Stefanie (Psychologische Förder- und Interventionsprogramme für das Kindes- und Jugendalter, 2009)

Förderung der Motivation zur körperlichen Aktivität durch telefonische und schriftliche Nachsorge für kardiologische Reha-Patienten - eine randomisierte Kontrollgruppenstudie - Bönisch, Rainer; Stemmler, Mark; Bremer, Franz-Josef; Schweidtmann, Werner; Ohnesorge, Willi; Muthny, Fritz A. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2013)
Ziel der Untersuchung war die Entwicklung und Evaluation einer telefonischen und schriftlichen Nachsorge-Maßnahme zur Förderung der Motivation zur körperlichen Aktivität nach einer stationären kardiologischen Anschlussheilbehandlung. Im Rahmen einer randomisierten Kontrollgruppenstudie wurden bei Patienten nach einer Anschlussheilbehandlung eine telefonische und schriftliche Nachsorge monatlich durchgeführt. Als Förderstrategien der Motivation wurden z. B. Ursachenzuschreibung des Reha-Erfolges auf Anstrengung, Erinnerung an die praktische Bedeutsamkeit körperlicher Aktivitäten für den Alltag und intrinsische Anreize eingesetzt. 6 Monate nach der Reha-Maßnahme erfolgte die Katamnese. Prä-Posttest-Daten von 202 Patienten wurden mittels Varianzanalysen und der Methode der geplanten Kontraste ausgewertet. Es zeigte sich für die telefonische Nachsorge im Vergleich zur Standard-Reha-Nachsorge der Kontrollgruppe ein kleiner aber signifikanter Effekt für gesundheitsbezogene Motivation. Intrinsische, soziale und Leistungsmotivation, krankheits- und bewegungsbezogene Ängste, allgemeine Angst und Depressivität sowie Teilnahme an einer ambulanten Herzsportgruppe wiesen keine signifikanten Unterschiede auf. Post-hoc-analytisch zeigten sich für die körperliche Aktivität (erfasst als Häufigkeit von Schwitzen und beschleunigtem Herzschlag) in den Interventionsgruppen signifikant höhere Werte als für die Kontrollgruppe. Insgesamt wird die Anwendung von Motivationsförderstrategien aus pädagogischen Kontexten als Erfolg bewertet. Eine unvollständige Umsetzung des Leitfadens, eine geringe Telefondauer- und häufigkeit sowie eine hohe Selbstselektion der Patienten werden neben Problemen bei der Quantifizierung körperlicher Aktivitäten als Ursache für die begrenzte Wirksamkeit angesehen.

Forschungsprojekt „Soziale Kompetenzen für Eltern und Kinder: Prävention dissozialer Entwicklungen und Förderung von Integration“. Gefördert durch das Bundesministerium für Familie, Senioren, Frauen und Jugend (Az. 214-2613/26). Zwischenbericht 2005 und erstes Halbjahr 2006 - Lösel, Friedrich; Beelmann, Andreas; Beer, Sabine; Hacker, Stefanie; Jaursch, Stefanie; Kabakci-Kara, Funda; Stemmler, Mark; Wallner, Susanne (2006)

Frühe universelle Prävention von dissozialen Entwicklungsproblemen: Implementation und Wirksamkeit eines verhaltensorientierten Elterntrainings - Beelmann, Andreas; Jaursch, Stefanie; Lösel, Friedrich; Stemmler, Mark (Praxis der Rechtspsychologie, 2006)

Functional dissociation between cognitive estimation and object naming in focal temporal and frontal lobe epilepsies - Braun, Isabella; Schwarz, Michael; Walther, Katrin; Stemmler, Mark; Kasper, Burkhard; Hamer, Hajo (International Journal of Epilepsy, 2018)

Gewalthaltige Computerspiele, problematisches Erziehungsverhalten und Jugenddelinquenz - Sauter, Katharina; Wallner, Susanne; Stemmler, Mark; Reinecke, Jost (Rechtspsychologie, 2016)

Gewaltprävention im Kindergarten - Jaursch, Stefanie; Lösel, Friedrich; Beelmann, Andreas; Stemmler, Mark (Frühe Förderung entwicklungsauffälliger Kinder und Jugendlicher, 2008)

Hardly any gender differences among opioid users in prison - Boksán, Klara; Weiss, M.; Geißelsöder, Kerstin; Dechant, Michael; Endres, J.; Breuer, M.; Stemmler, Mark; Wodarz, N. (Forensische Psychiatrie, Psychologie, Kriminologie, 2023)
Background A high proportion of incarcerated women exhibit opioid dependence. Concerning the question whether women and men differ in their opioid use and whether empirical evidence for a telescoping effect (later initiation of drug use with accelerated progression of dependence) in women can be found, the research situation is ambiguous. In this respect, there is a lack of studies on possible gender differences, particularly in the correctional setting.Objective In a sample of n = 247 opioid-dependent individuals incarcerated in Bavarian prisons we compared female (n = 31) and male (n = 216) study participants regarding age, drug use, substitution treatment, psychological preload, education, and economic situation.Method Data were collected during an initial interview in prison as part of the ongoing study "Incarceration and opioid dependence-an evaluation study ".Results There were no differences in drug use between the two gender groups; consequently, no evidence of a telescoping effect among opioid-dependent female prisoners was found. Furthermore, no differences between women and men regarding substitution treatment, education, and economic situation were found. Women were more likely to report having suffered from depression prior to incarceration and having experienced sexual abuse.Conclusion Evidence was found of greater psychological distress among female compared with male incarcerated persons with opioid dependence, but strikingly few differences beyond that. It seems conceivable that in this population a particularly severe course of opioid dependence could be present, which makes any gender-specific differences recede into the background.
CRIS-Team WoS Importer:2023-01-27

Imputing missing data values in repeated measurement within-subjects designs - Bingham, C. Raymond; Stemmler, Mark; Petersen, Anne C.; Graber, Julia A. (Methods of Psychological Research, 1998)
Introduces a procedure for inputing missing data values in repeated measurement within-subjects designs. Two sets of simulations were performed. The first used a single data set to examine the influence of the proportion of cases with missing values, the number of repeated measures, and the shape of the individual response curve on the discrepancy between the imputed and observed data, and to compare this method with mean-substitution. A Monte Carlo simulation was also conducted which examined the proportion of cases with missing values, the shape of the individual response curve, and the sample size in relation to the discrepancy between the observed and imputed standard errors and moments. Results indicated that the imputed data closely approximated observed values, that estimation improved as the number of repeated measures increased and proportion of cases with missing values decreased, and that sample sizes greater than 100 provided equivalent results.
Keywords: imputing missing data values; repeated measurement within subjects designs

Inanspruchnahme psychosozialer Hilfen bei jungen Erwachsenen mit suizidalem Erleben und Verhalten - Weiss, Maren; Hildebrand, Anja; Stemmler, Mark (Psychotherapie Psychosomatik Medizinische Psychologie, 2024)
The study explores the utilization of psychosocial support by young adults facing suicidal ideation or impulses, considering a comprehensive spectrum of psychosocial services. The study sheds light on help utilization and gaps in service use among different groups. The data is derived from the baseline assessment of the research project "Outcome Evaluation [U25]". The sample includes 888 young adults who reported suicidal thoughts and behaviors. Among the participants, 55 % accessed at least one psychosocial service. Medical/psychotherapy services were the most utilized (54 %), followed by professional counseling (34 %) and non-professional self-help services (22 %). Gender differences were observed, with males using help less frequently than females and individuals with diverse gender identities. Participants in relationships were less likely to seek help than singles. A migrant background showed no consistent impact on service utilization. Psychological distress and suicide literacy were associated with increased service utilization. Regression analysis revealed that gender and relationship status remained predictors of service utilization even when considering mental distress, suicidal thoughts and behaviors, and suicide literacy.
CRIS-Team Scopus Importer:2024-10-11
Keywords: suicidal thoughts and behaviors; suicide literacy; utilization of mental health services; young adults

Inkonsistenz im Erziehungsverhalten zwischen Müttern und Vätern und Verhaltensprobleme des Kindes - Jaursch, Stefanie; Lösel, Friedrich; Beelmann, Andreas; Stemmler, Mark (Psychologie in Erziehung und Unterricht, 2009)

„Intention to treat“ oder „treatment as received“ - der Umgang mit Abbrechern in der Forschung zur Straftäterbehandlung: Methodische Überlegungen und Beispiele aktueller Studien - Endres, Johann; Breuer, Maike Miriam; Stemmler, Mark (Forensische Psychiatrie, Psychologie, Kriminologie, 2016)

Item Response Theory (IRT) analysis of the SKT Short Cognitive Performance Test - Stemmler, Mark; Keller, Ferdinand; Fasan, Raphaela (Psychological Test and Assessment Modeling, 2019)
In this article, the SKT Short Cognitive Performance Test (SKT = Syndrom Kurztest; Erzigkeit, 2001) was tested with models of IRT. Here, the SKT test functions as an example on how IRT- analyses with any cognitive test, which results in a summary score, can be applied. The SKT was newly scaled in 2015 (Stemmler, Lehfeld & Horn, 2015) using a regression-based continuous norming approach (Crawford & Garthwaite, 2006) while leaving the testing material unchanged. The data were from a sample of 811 older adults ( x  73.3 years; SD=7.2) assessed at multiple testing sites in Germany. The sample consisted of cognitively healthy older adults (n =250), of older adults suffering from mild cognitive impairment (MCI; n=290) as well as adults suffering from dementia (n=271). Analyses to check the psychometric validity of the SKT encompass the Partial Credit Model (PCM), the Graded Response Model (GRM) and Multidimensional Response Models (MRM). The strict assumptions of the one parametric Rasch model with regard to specific objectivity were not met. The two parametric GRM provided a better goodness-of-fit. A two-dimensional GRM revealed that the subtests assessing Memory and those assessing Attention can be distinguished as two separate dimensions. However, the use of a total score seems still valid, but, next to a careful inspection of the total score the scores for Memory and Attention should be taken into account and considered separately.

Jugendliche Gewaltdelinquenz, psychosoziale Merkmale und Migrationsstatus - Wallner, Susanne; Stemmler, Mark (Forensische Psychiatrie, Psychologie, Kriminologie, 2014)
Im Rahmen der Längsschnittstudie „Chancen und Risiken im Lebensverlauf“ wird die Entstehung devianten und delinquenten Verhaltens untersucht. Die Datengrundlage der vorliegenden Arbeit bilden die Selbstberichte von männlichen Neuntklässlern aus Dortmunder und Nürnberger Schulen (n  = 726). Ausgewertet wurden insbesondere die Angaben zur Täterschaft im letzten Jahr, die u. a. Dunkelfelddaten zu Gewaltdelikten umfassen. Die Täterindizes zu Gewaltkriminalität wurden unter Berücksichtigung der Schulart und des Migrationsstatus mit psychosozialen Merkmalen (z. B. gewaltakzeptierenden Einstellungen, egozentrischen Persönlichkeitsmerkmalen, erlebter körperlicher Bestrafung in der Erziehung) in Beziehung gesetzt, die aus entwicklungspsychopathologischer Sicht zu Jugenddelinquenz und Gewalt beitragen können. Insgesamt legen die empirischen Befunde nahe, dass Jugendliche mit Migrationshintergrund im Vergleich zu Jugendlichen ohne Migrationshintergrund signifikant höhere Werte in Bezug auf Gewalt- und Peer-Delinquenz aufweisen. Die Unterschiede zwischen Gewalttätern und Nichtgewalttätern bzw. Jugendlichen mit Migrationsstatus und Jugendlichen ohne Migrationsstatus gehen z. T. auf verschiedene Ausprägungen psychosozialer Merkmale zurück. Zusätzliche relativierende Ergebnisse zu schulartspezifischen Auswertungen ergänzen die Darstellung. Einschränkungen der vorliegenden Arbeit werden erörtert, und Implikationen für zukünftige Forschungsarbeiten zu Jugendgewalt werden vor dem Hintergrund möglicher Ansätze der Gewaltprävention und -intervention diskutiert.
Keywords: Jugenddelinquenz; Gewalt; Schülerbefragung; Migrationsstatus

Konfigurale Auswertung von Daten aus Prätest-Posttest Kontrollgruppen Designs - Stemmler, Mark; Masendorf, Friedrich (Zeitschrift für Klinische Psychologie, Psychiatrie und Psychotherapie, 1998)
Examines methods of configural frequency analysis (CFA) for treatment evaluation in multivariate pretest–posttest designs. Three CFA methods are proposed: prediction CFA, interaction CFA and generalized unary hypothesis analysis. These methods are compared and evaluated. Data from a prior experiment are used to assess the effect of training methods on calculation and learning methods in learning disabled children using CFA methods. The effect on pretest–posttest designs are assessed using numerical analysis.
Keywords: Experimental Design; Multivariate Analysis; Treatment Effectiveness Evaluation; Methodology; Pretesting

Konfigurationen und Latente Klassen aus PISA Kompetenzen und dem „Migrationshintergrund“ mit Kovariaten - Heine, Jörg-Henrik; Stemmler, Mark (Klassifikationsanalysen in Theorie und Praxis – Jubiläumsband 25 Jahre AKA-Rothenberge, 2021)
Keywords: Konfigurationsfrequenzanalyse (KFA); Latente Klassenanalyse

Längsschnittliche Zusammenhänge zwischen Erziehungsgewalt und Gewaltdelinquenz im frühen Jugendalter - Weiss, Maren; Link, Eva; Stemmler, Mark (Rechtspsychologie, 2015)
Obwohl körperliche Züchtigung in der Erziehung gesetzlich verboten ist, sind zumindest „mildere“ Formen von Erziehungsgewalt nach wie vor weit verbreitet. Mögliche negative Auswirkungen auf die psychosoziale Entwicklung des Kindes sind vielfältig und reichen von internalisierenden Problemen bis zu Gewalttätigkeit. In der vorliegenden Studie wird der Zusammenhang zwischen erlebter Erziehungsgewalt und psychischen und sozialen Anpassungsproblemen im Jugendalter untersucht. Besonders berücksichtigt werden dabei die Schwere und Persistenz der Erziehungsgewalt sowie die Einstellung zur Gewalt der Jugendlichen. Datengrundlage der Untersuchung bilden die Selbstberichte von Schülern aus Dortmund und Nürnberg (n = 836), welche wiederholt im Alter von 11, 12 und 13 Jahren (5. bis 7. Jahrgangsstufe) befragt wurden. Neben Fragen zu elterlichen Erziehungspraktiken, Gewaltakzeptanz, Sozialverhalten und Freundschaften liegen Angaben zu devianten und delinquenten Verhaltensweisen vor. Die Ergebnisse zeigen, dass schon eine geringe Ausprägung an erlebter elterlicher Gewalt signifikante negative Entwicklungseffekte hat. Bei gewalthaltig erzogenen Jugendlichen zeigten sich emotionale und soziale Probleme im Allgemeinen sowie ein erhöhtes Risiko für Gewaltdelinquenz im Speziellen (jedoch kein erhöhtes Risiko für andere Delikte). Zusätzlich konnte die Bedeutung von Schwellen verdeutlicht werden, denn bei schwerer und kontinuierlicher Gewalterfahrung war die Gewaltdelinquenz besonders hoch. Der Zusammenhang zwischen erlebter Erziehungsgewalt und eigener Gewalttätigkeit scheint dabei zumindest teilweise über eine erhöhte Gewaltakzeptanz vermittelt zu werden. Aufgrund unseres längsschnittlichen Designs gehen diese Befunde über die übliche Korrelationsforschung hinaus, die lediglich den Zusammenhang zwischen gewalthaltiger Erziehung und antisozialem Verhalten repliziert. Die Daten bestätigen, dass das Ideal der gewaltfreien Erziehung noch nicht in der Mitte der Gesellschaft angekommen ist, was präventive Bemühungen zur Verbesserung der Erziehungskompetenz weiterhin rechtfertigt.

Latent Growth Curve Modeling and the Study of Problem Behavior in Girls - Stemmler, Mark; Petersen, Anne C. (Antisocial behavior and crime: Contributions of developmental and evaluation research to prevention and intervention, 2012)

Life adversities of clients seeking advice for suicidal ideation from an online peer counseling service: Characteristics and associations with outcomes - Hildebrand, Anja; Weiss, Maren; Stemmler, Mark (Mediterranean Journal of Clinical Psychology, 2023)
Objective: [U25] Germany is a low-threshold, anonymous and free-of-charge online suicide prevention service for people up to 25 years of age. Its special feature is that counseling is provided by trained and continuously supervised voluntary peers. This study addresses the following research questions: (1) Which life adversities are reported by the clients of [U25]? (2) Are the life adversities intercorrelated? (3) According to patients, do life adversities change during the counseling process? (4) What are the associations between life adversities and outcome measures (e.g., reduction in suicidality or improvement in general situation)? Method: Data was collected through an online survey (n = 318). To measure psychological burden, the presence of 16 life adversities (e.g., problems in relationships) was assessed retrospectively. As the dependent variable, the change in suicidality was measured by means of three newly created items. In addition, a short form of the Bochum Change Questionnaire 2000 (BCQ 2000) was used to assess the patients’ subjectively perceived change due to counseling. Results: Regarding life adversities, the clients were heavily burdened. Throughout the course of counseling, many clients’ situations improved, at least concerning several adversities. Some life adversities significantly correlate with each other, but the correlation is mostly small to moderate. Suicidality is positively correlated with self-harming behaviors and loss of someone close to the advice seekers. Conclusions: Possible starting points for improving online counseling for suicidal adolescents and young adults are discussed.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Adolescence; Life adversities; Online counseling; Peer counseling; Suicide prevention

Log-linear modeling and two-sample CFA in the search of discrimination types - Stemmler, Mark Kurt; Bingham, C. Raymond; Stemmler, Mark (Psychology Science, 2003)
Keywords: two-sample comparison; Configural Frequency Analysis (CFA); two-sample CFA; log-linear modeling (LLM); nonparametric testing; contingency table analysis

Long-term evaluation of a bimodal universal prevention program: Effects on antisocial development from kindergarten to adolescence - Lösel, Friedrich; Stemmler, Mark; Bender, Doris (Journal of Experimental Criminology, 2013)
Objectives Only a handful of studies on developmental crime prevention contain very long-term evaluations and all these addressed high-risk groups in English-speaking countries. In contrast, this article investigates long-term outcomes of a bimodal universal prevention program within the Erlangen-Nuremberg Development and Prevention Study (ENDPS) in Germany. Methods The ENDPS is a combined prospective longitudinal and experimental project that originally consisted of 675 kindergarten children from 609 families who were nearly representative for the local area. In the prevention part of the project, a group-wise randomization and matched pairs design was used to evaluate a training of children’s social problem solving skills, a parent training on positive parenting behavior, and a combination of both programs. Originally, 239 children were each in the program group and control group. Outcomes were measured after ca. 3 months, and 2, 5, and 10 years. The outcome measures varied over time and contained, inter alia, reports on child behavior in the Social Behavior Questionnaire (SBQ) from kindergarten teachers, school teachers, mothers, and the youngsters themselves. The overall retention rates in the ENDPS were satisfactory (e.g., 90 % after 10 years), but missing data from various informants further reduced the groups over time. The outcome evaluation was mainly carried out by causal regression models. Results There were various desirable effects of the program not only in the short and medium term but also after 5 and 10 years, i.e. on externalizing behavior, property offences, and total behavioral problems. The significant effects were mostly small (d = .23–.59) and significances became rare over time. As a trend, the combined parent and child training and the child training alone were more effective; however, this was not consistent across all follow-ups. The outcomes did not only vary with regard to time but also between different measures and informants. The youth self-reports and teacher reports were more suitable to detect effects than the mothers’ reports. Children at higher risk seemed to benefit most from the intervention; however, this was also not fully consistent across measures and times. Conclusions The various desirable effects of a relatively short and inexpensive universal program are in accordance with a public health approach in developmental crime prevention. However, it should not be seen as an alternative to selective and indicated approaches, but as a ‘foot in the door’ for high-risk children and families that need more intensive and costly programs. The variations in results across time, outcome measures, informants, and program components confirm the heterogeneity of meta-analytic findings in the field. Therefore, one must be aware of ‘fishing for significances’ and research on ‘what works’ should go beyond the content of programs. More studies should investigate how characteristics of program delivery, contexts, participants, and evaluation methods contribute to effectiveness.

Long-term follow-up of a multimodal day clinic, group-based treatment program for patients with very high risk for complex posttraumatic stress disorder, and for patients with non-complex trauma-related disorders - Bever-Philipps, Anke; Silbermann, Andrea; Morawa, Eva; Schäflein, Eva; Stemmler, Mark; Erim, Yesim (Frontiers in Psychiatry, 2023)
Objective: The present study examined the follow-up of a multimodal day clinic group-based therapy program for patients with trauma-related disorders and investigated potential differences for patients with classic PTSD versus cPTSD. Method: Sixty-six patients were contacted 6 and 12 months after discharge of our 8-week program and completed various questionnaires (Essen Trauma Inventory (ETI), Beck Depression Inventory-Revised (BDI-II), Screening scale of complex PTSD (SkPTBS), Patient Health Questionnaire (PHQ)-Somatization, as well as single items to therapy utilization and life events in the interim period). Due to organizational reasons a control group could not be included. Statistical analyses included repeated-measures ANOVA with cPTSD as between-subject factor. Results: The reduction of depressive symptoms at discharge was persistent at 6 and 12 months follow-up. Somatization symptoms were increased at discharge, but were leveled out at 6 months follow-up. The same effect was found for cPTSD symptoms in those patients with non-complex trauma-related disorders: Their increase of cPTSD symptoms was flattened at 6 months follow-up. Patients with a very high risk for cPTSD showed a strong linear reduction of cPTSD symptoms from admission to discharge and 6 months follow-up. cPTSD patients had a higher symptom load compared to patients without cPTSD on all time points and scales. Conclusion: Multimodal, day clinic trauma-focused treatment is associated with positive changes even after 6 and 12 months. Positive therapy outcomes (reduced depression, reduced cPTSD symptoms for patients with a very high risk for cPTSD) could be maintained. However, PTSD symptomatology was not significantly reduced. Increases in somatoform symptoms were leveled out and can therefore be regarded as side effects of treatment, which may be connected with actualization of trauma in the intensive psychotherapeutic treatment. Further analyses should be applied in larger samples and a control group.
CRIS-Team Scopus Importer:2023-07-21
Keywords: CPTSD; day clinic; follow-up; group therapy; psychotherapy; PTSD; trauma

Methodische Zugänge der Intervention und Evaluation - Stemmler, Mark (Handbuch Sozialisationsforschung, 2015)

Mittelfristige Effekte des Präventionsprogramms EFFEKT-E für emotional-belastete Mütter und ihre Kinder unter besonderer Berücksichtigung mütterlicher Belastungen - Kötter, Charlotte; Stemmler, Mark; Lösel, Friedrich; Bühler, Anneke; Jaursch, Stefanie (Zeitschrift für Gesundheitspsychologie, 2011)
Zusammenfassung. Kinder (subklinisch) depressiver Mütter haben ein erhöhtes Risiko, Verhaltensauffälligkeiten auszubilden. Einige der Faktoren der Transmission liegen direkt in der Interaktion, wie das Erziehungsverhalten. Weitere Risikofaktoren wie Alleinerziehendenstatus oder geringe soziale Unterstützung können die Auswirkungen auf die Kinder noch verstärken. Da Erlebens- und Verhaltensprobleme häufig bereits im Vorschulalter auftreten, sollten Präventionsprogramme möglichst früh ansetzen. Dem folgt die vorliegende Studie, die in 13 Mutter-Kind-Kliniken durchgeführt wurde. Geprüft wurde, ob Kinder von emotional und sozial belasteten Müttern von einem Präventionsprogramm (EFFEKT-E) profitieren, das einen Erziehungskurs für Mütter und ein soziales Kompetenztraining für Kinder umfasst. Dazu wurden 194 Mütter mit 4- bis 7-jährigen Kindern in der Kontrollgruppe und 169 Mütter in der Interventionsgruppe in einem Vortest-Nachtest-Design untersucht. Abhängige Variablen waren kindliche Erlebens- und Verhaltensprobleme sowie das mütterliche Erziehungsverhalten und Kompetenzerleben. Neben allgemeinen Effekten wurden eventuelle Moderatoreffekte von mütterlichen Risikofaktoren geprüft. Es zeigten sich positive kurzfristige Effekte auf das kindliche Problemverhalten. Mittelfristige positive Effekte gab es bei der elterlichen Kompetenzeinschätzung (Sechs-Monats-Follow-up). Dies galt insbesondere für Mütter, die eine hohe soziale Unterstützung erlebten. Die Ergebnisse werden unter methodischen und praktischen Gesichtspunkten diskutiert.

Motivation zum kardiologischen Reha-Sport - Ergebnisse zur Reliabilität und Validität eines neu entwickelten Fragebogens (MokaRSpo) - Bönisch, Rainer; Bremer, Franz-Josef; Schweidtmann, Werner; Ohnesorge, Willi; Stemmler, Mark; Muthny, Fritz A. (Prävention und Rehabilitation, 2009)

Motivation zur körperlichen Aktivität, Ängste und Depressivität im Rehabilitationsverlauf kardiologischer Patienten und Vorhersage des Reha-Erfolges - Bönisch, Rainer; Stemmler, Mark; Bremer, Franz-Josef; Schweidtmann, Werner; Ohnesorge, Willi; Muthny, Fritz A. (Praxis klinische Verhaltensmedizin und Rehabilitation, 2011)

Mütterliche Depressivität, Erziehung und kindliche Erlebens- und Verhaltensprobleme - Kötter, Charlotte; Stemmler, Mark; Bühler, Anneke; Lösel, Friedrich (Kindheit und Entwicklung, 2010)
The following research questions were investigated: What kind of impairments exist in the parenting behavior of emotionally burdened mothers as well as in the behavior of their children aged 4-7 years? What are the existing correlations between maternal depression, different aspects of parenting, and the child's emotional and behavioral problems? Which aspects of parenting mediate the relationship? Subclinically depressed mothers (N = 380) filled in standardized questionnaires about parenting behavior, perceived competence and stress, and their child's behavior. The data were compared to a normative sample (Losel et al., 2005). Children of depressed mothers showed significantly more emotional and behavioral problems. The stressed and depressed-feeling mothers showed more inappropriate parenting behavior in comparison to the normative mothers. In addition, these mothers rated themselves less competent in parenting, and they reported more parental stress. It is shown that perceived parenting competence and stress mediate the relationship of maternal depression and children's emotional and behavioral problems. The impact of the results on prevention is discussed.
Keywords: parenting; emotional and behavioral problems; maternal depression; parenting stress

Nachbericht zur Evaluation des Bundesprogramms „Elternchance ist Kinderchance – Elternbegleitung der Bildungsverläufe der Kinder“. Bericht zur Kontrollgruppe im Modul 3 – die Wirkung auf Ebene der Eltern und Kinder - Beck, Mira; Schwaß, Mariann; Stemmler, Mark (2016)

Nonparametrical analysis of change patterns in dependent samples - Stemmler, Mark (Methods of Psychological Research, 1998)
If the assumptions for repeated measures analysis of variance are violated, nonparametrical statistical tools need to be applied. Two methods for the evaluation of interindividual differences in intraindividual change are suggested: One method follows the configural frequency analysis approach of analyzing change patterns, the other is from Latent Class Analysis (LCA) and its special version for repeated measures, latent Markov modeling. Differential and complementary aspects of the two methods are discussed.

Nonparametric testing of improvement scores in a two sample prepost design - Stemmler, Mark; Bingham, C. Raymond (Psychology Science, 2004)

Normative versus ipsative configural frequency analysis in personality research - Köhler, Thomas; Stemmler, Mark (European Journal of Personality, 1997)
Configural frequency analysis (CFA) tests whether certain individual patterns in different variables are observed more frequently in a sample than expected by chance. In normative CFA, these patterns are derived from the S's specific position in relation to sample characteristics such as the median or the mean. In ipsative CFA, patterns are defined within an individual reference system, e.g., relative to the S's median of different variable scores. Normative CFA examines dimensionality of scales and is comparable to factor analysis in this respect. Ipsative CFA rather yields information about location of scores in different variables, in a similar way to ANOVA or Friedman testing. However, both normative and ipsative CFA may supply information not obtainable by means of the aforementioned methods. This is illustrated in a reanalysis of data in 4 scales of an anxiety inventory.
Keywords: Anxiety; Frequency Distribution; Personality Measures; Statistical Analysis

Online Peer Counseling for Suicidal Ideation: Participant Characteristics and Reasons for Using or Refusing This Service - Weiss, Maren; Hildebrand, Anja; Braun-Scharm, Hellmuth; Stemmler, Mark (Psych, 2021)
[U25] is a German online-peer-counseling service for adolescents with suicidal ideation, who typically do not seek or receive adequate counseling. We conducted an online survey in order to compare persons who receive online counseling by [U25] compared to those who are visitors of [U25] websites but do not (yet) receive counseling. Via online survey, all visitors to the [U25] websites were invited to fill in a questionnaire on sociodemographic data, utilization reasons, and barriers. Our final sample consisted of n = 318 counseling clients, n = 1127 persons who have not yet sought help but intend to do so (“prospective clients”), and n = 444 persons who do not consider [U25] counseling for themselves (“refusers”). Clients were more often female and showed positive attitudes toward online counseling. Low perceived need for counseling was the most frequent barrier reported by the refusers, whereas fear of stigma and practical barriers were rarely reported; younger and male refusers reported needing to write down one’s problems as a barrier more often. Self-selection might reduce generalizability of our results. Online counseling can facilitate receiving psychosocial support for young persons with suicidal ideation, particularly if barriers are addressed.<br
Keywords: suicide prevention; adolescents; online counseling; peer counseling; utilization barriers

Online-Peer-Suizid-Präventionsprogramme bei Jugendlichen und jungen Erwachsenen: Eine systematische Übersichtsarbeit - Hildebrand, Anja; Weiss, Maren; Stemmler, Mark (Zeitschrift für Psychiatrie, Psychologie und Psychotherapie, 2019)

Opioid substitution treatment, relapse and addiction-related outcomes in prison setting and after release: A longitudinal study - Geißelsöder, Kerstin; Weiss, Maren; Boksán, Klara; Dechant, Michael; Endres, Johann; Breuer, Maike; Stemmler, Mark; Wodarz, Norbert (Nordic Studies on Alcohol and Drugs, 2024)
Aims: Opioid addiction is a common problem among prisoners. The aim of this study was to examine differences between people who are incarcerated receiving opioid substitution treatment (OST) and those not receiving OST on addiction-related outcome variables during incarceration and after release from prison. Variables covered illicit use of opioids, non-prescribed substitution medication and other substances, opioid withdrawal symptoms, opioid craving, non-fatal overdoses and post-release substitution treatment. Design: Interviews (European Addiction Severity Index, EuropASI) were conducted with 247 participants in German prisons before release. Participants were interviewed again 1 month and 3–6 months after release from prison. Results: During incarceration, participants who received OST used less illicit opioids and non-prescribed substitution medication than those who did not receive OST. After release from prison, participants in the OST group reported less illicit opioid use and less non-prescribed substitution medication use, as well as less opioid craving. Participants who received OST in prison were more likely to be in OST at post-release follow-up than those who had not received in-prison OST. Conclusion: OST appears to have a positive effect on illicit opioid use and craving both in prison and after release, as well as on treatment at follow-up, which can be considered a protective factor.
Created from Fastlane, Scopus look-up
Keywords: opioid addiction; opioid substitution treatment; prison

Parenting stress and the reliability of parental information in the diagnostics of children and adolescents with symptoms of psychiatric and behavioral disorders - Irlbauer-Müller, Viktoria; Eichler, Anna; Stemmler, Mark; Moll, Gunther; Kratz, Oliver (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2017)
Information from parents is regularly used in the diagnostic process of children and adolescents with psychiatric symptoms. But the reliability of this information is debatable, because the parents' own stress can distort their perceptions of the child's symptoms.For each of N = 68 children and adolescents (11-18 years) who were using mental health services for the first time, we evaluated the ratings of a parent and a professional clinician (internalizing, externalizing symptoms, total-problem score). In addition, parenting stress was scored on the Eltern-Belastungs-Inventars (EBI, Tröster, 2011), which measures both child-related stress and parent-related stress as well as total stress.Highly stressed parent ratings differed more from the clinicians' ratings than the ratings of less stressed parents. Additionally, correlations showed that higher parenting stress resulted in larger differences between the parent's and the clinician's assessments. Multiple regressions proved the predictive value of child-caused parenting stress for these differences. These results apply for internalizing symptoms, externalizing symptoms, and total-problem score.Parenting stress should be evaluated systematically in order to carefully assess the value of the information from parents and to determine how it should be included in diagnostic and therapeutical decisions.
EVALuna2:23890

Person-Centered Data Analysis With Covariates and the R-Package confreq - Stemmler, Mark; Heine, Joerg-Henrik; Wallner, Susanne (Methodology, 2021)
Configural Frequency Analysis (CFA) is a useful statistical method for the analysis of multiway contingency tables and an appropriate tool for person-oriented or person-centered methods. In complex contingency tables, patterns or configurations are analyzed by comparing observed cell frequencies with expected frequencies. Significant differences between observed and expected frequencies lead to the emergence of Types and Antitypes. Types are patterns or configurations which are significantly more often observed than the expected frequencies; Antitypes represent configurations which are observed less frequently than expected. The R-package confreq is an easy-to-use software for conducting CFAs; another useful shareware to run CFAs was developed by Alexander von Eye. Here, CFA is presented based on the log-linear modeling approach. CFA may be used together with interval level variables which can be added as covariates into the design matrix. In this article, a real data example and the use of confreq are presented. In sum, the use of a covariate may bring the estimated cell frequencies closer to the observed cell frequencies. In those cases, the number of Types or Antitypes may decrease. However, in rare cases, the Type-Antitype pattern can change with new emerging Types or Antitypes.
CRIS-Team WoS Importer:2021-07-16

Person-centered methods: Configural Frequency Analysis (CFA) and Other Methods for the Analysis of Contingency Tables - Stemmler, Mark (Springer, 2014)
This book takes an easy-to-understand look at the statistical approach called the person-centered method. Instead of analyzing means, variances and covariances of scale scores as in the common variable-centered approach, the person-centered approach analyzes persons or objects grouped according to their characteristic patterns or configurations in contingency tables. The main focus of the book will be on Configural Frequency Analysis (CFA; Lienert and Krauth, 1975) which is a statistical method that looks for over and under-frequented cells or patterns. Over frequented means that the observations in this cell or configuration are observed more often than expected, under-frequented means that this cell or configuration is observed less often than expected. In CFA a pattern or configuration that contains more observed cases than expected is called a type; similarly, a pattern or configuration that is less observed than expected are called an antitype. CFA is similar to log-linear modeling. In log-linear modeling the goal is to come up with a fitting model including all important variables. Instead of fitting a model, CFA looks at the significant residuals of a log-linear model. The book describes the use of an R-package called confreq (derived from Configural Frequency Analysis). The use of the software package is described and demonstrated with data examples.

Person-Centered Methods: Configural Frequency Anaylsis (CFA) and Other Methods for the Analyis of Contingency Tables - Stemmler, Mark (Springer, 2020)

Prävalenz und Verlauf von Kinder- und Jugenddelinquenz: Ergebnisse des Projekts "Chancen und Risiken im Lebensverlauf (CURL)" - Stemmler, Mark; Wallner, Susanne; Weiss, Maren (Festschrift für Franz Streng zum 70. Geburtstag, 2017)

Prävention von Bullying - Weiss, Maren; Stemmler, Mark (Psychologische Förder- und Interventionsprogramme für das Kindes- und Jugendalter., 2021)

Prävention von Problemen des Sozialverhaltens im Vorschulalter: Evaluation des Eltern- und Kindertrainings EFFEKT - Jaursch, Stefanie; Beelmann, Andreas; Lösel, Friedrich; Stemmler, Mark (Kinderschutzzentrum, 2009)

Prävention von Problemen des Sozialverhaltens im Vorschulalter: Evaluation des Eltern- und Kindertrainings EFFEKT - Lösel, Friedrich; Beelmann, Andreas; Stemmler, Mark; Jaursch, Stefanie (Zeitschrift für Klinische Psychologie und Psychotherapie, 2006)
Theoretischer Hintergrund: In Deutschland herrscht ein Mangel an methodisch kontrollierten Evaluationen von Programmen zur Prävention von Verhaltensproblemen bei Kindern und Jugendlichen. Fragestellung: Die vorliegende Studie evaluiert die Wirksamkeit eines Kindertrainings, eines Elterntrainings sowie einer Kombination aus beiden Programmen. Methode: Aus einer Stichprobe von 675 Kindergartenkindern und ihren Familien nahmen 227 an einer der drei Trainingsbedingungen teil, 227 Kinder dienten als äquivalente Kontrollgruppe. Erfolgsmaße wurden 2–3 Monate sowie bis zu 24 Monate nach Abschluss der Trainings erhoben. Sie bestanden aus den Angaben von Erzieherinnen im Preschool Social Behavior Questionnaire sowie aus Inhaltsanalysen von Schulzeugnissen der 1. Klasse. Ergebnisse: Die Trainings führten zu kurzzeitigen positiven Effekten bei Problemen des Sozialverhaltens, der Hyperaktivität/Unaufmerksamkeit und emotionalen Störungen. Die deutlichsten Effekte zeigten sich bei den kombinierten Programmen und bei Kindern mit ausgeprägteren Problemen des Sozialverhaltens. Die Langzeiteffekte in den verschiedenen Trainingsbedingungen waren weniger konsistent. Es zeigte sich aber eine generelle Reduktion multipler Verhaltensprobleme in der Schule. Schlussfolgerung: Die Ergebnisse stimmen mit internationalen Meta-Analysen überein und rechtfertigen einen vorsichtigen Optimismus hinsichtlich derartiger Präventionsprogramm
Keywords: Prävention; Probleme des Sozialverhaltens; Kindertraining; Elterntraining; Evaluation

Predicting cognitive decline and dementia with the newly-normed SKT Short Cognitive Performance Test - Stemmler, Mark; Hessler, Johannes Balthasar; Bickel, Horst (Dementia and Geriatric Cognitive Disorders Extra, 2019)
Objective: The aim of this article was to determine the criterion-related validity of the newly-normed SKT Short Cognitive Performance Test with the onset of dementia as the predicted criterion. Methods: The cognitive ability was tested with the SKT in a sample of 546 cognitively healthy adults aged 65 to 85 years. New cases of MCI or dementia were determined in three follow-up investigations at one-year intervals. Each participant’s cognitive status was rated on the Clinical Dementia Rating Scale (CDR). The cognitive status according to the SKT is presented in terms of a traffic light system. Results: Based on Kaplan-Meier estimators, the trajectories of the different SKT traffic light labels were investigated over three years. The trajectories were significantly different, representing differential risks for dementia onset. In comparison to the green group, the hazard ratio (HR) for the development of dementia and MCI amounted to HR = 6.63 (95% CI: 2.75-15.96) and HR = 2.34 (95% CI: 1.37-3.99), respectively, in the yellow group, and to HR = 25.40 (95% CI: 10.73-60.14) and HR = 3.83 (95% CI: 1.86-7.86), respectively, in the red group. Conclusions: The newly-normed SKT showed a high predictive validity for the onset of dementia
Keywords: MCI. cognitive tests; Syndrom Kurztest (SKT); predictive validity; Cox regression; dementia; cognitive impairment

Prediction of Antisocial Development in Childhood and Youth Using the Cracow Instrument: Predictive Validity of a Structured Risk/Need Assessment Instrument - Wallner, Susanne; Lösel, Friedrich; Stemmler, Mark (International Conference on Psychology & Law - „EAPL & World 2015“, 2015)

Prediction of response to total sleep deprivation by autonomic heart rate parameters? - Rechlin, Thomas; Hegmann, Harald; Weis, Maria; Stemmler, Mark; Claus, Detlef; Kaschka, Wolfgang (Biological Psychiatry, 1995)
Keywords: Sleep deprivation; heart rate variability; autonomic parameters

Preterm small-for-gestational age children: Predictive role of gestational age for mental development at the age of 2 years - Nögel, Stephanie; Deiters, Ludger; Stemmler, Mark; Rascher, Wolfgang; Trollmann, Regina (Brain & Development, 2015)
AIM: The aim of the study was to compare the cognitive development of very low birth weight (VLBW) preterm SGA children and preterm AGA children at the age of 2 years. The hypothesis was that SGA children are at an additional risk for deficits in cognitive function. Additionally, the impact of neonatal risk factors and the parents' profession on the early cognitive development was analysed. METHODS: Cognitive function of 107 preterm infants with a gestational age of 24-35 weeks was assessed with the Mental Bayley Scales of Infant Development at the age of 2 years (mean±SEM). The results of SGA (n=38) and AGA (n=69) children were compared as well as neonatal risk factors and parental education. RESULTS: There was a linear regression between the Mental Bayley Scales result and gestational age for preterm infants with a gestational age of 24-32 weeks. SGA and AGA children did not differ significantly in their cognitive function at the age of 2 years. A strong association was found between the parents' profession and cognitive development. Among the neonatal risk factors, bronchopulmonary dysplasia was a strong predictor of mental development. INTERPRETATION: Cognitive development of two-year-old preterm children with a gestational age of 24-32 weeks was mainly related to their gestational age. Being born preterm and small for gestational age was not additionally associated with cognitive deficits at the age of 2 years. The parents' profession had a significant impact on the cognitive development. The role of the parents' profession on the early development of preterm infants should be elucidated in further studies. Copyright © 2014 The Japanese Society of Child Neurology. Published by Elsevier B.V. All rights reserved.
Keywords: Gestational age; Mental development; Parental profession; Preterm infants

Preventing child behavior problems at preschool age: The Erlangen-Nuremberg Development and Prevention Study - Lösel, Friedrich; Stemmler, Mark (International journal of conflict and violence, 2012)
A brief overview of the prevention part of the long-term Erlangen-Nuremberg Development and Prevention Study, which combines a prospective longitudinal and experimental design. Findings up to five years after intervention are reported. From a sample of 609 families with kindergarten children, subgroups participated in the universal prevention program EFFEKT (child social skills training, a parent training and a combination of both) or were assigned to equivalentcontrol groups. The short-term evaluation showed significant effects in mediating constructs (social problem solving and parenting behavior) and in educators’ ratings of children’s social behavior. In a follow-up after two to three years, school report cards showed fewer children with multiple behavior problems. In a further follow up after four to five years program children reported fewer externalizing and internalizing problems than the control group. There were no significant effects in the mothers’ reports on their children’s behavior. Most significant effect sizes ranged between d = 0.20 and d = 0.40. The findings suggest various positive long-term effects of the intervention. However, one need to be cautious with regard to over-generalizing the positive findings, because effect sizes vary over time and the positive findings could not be replicated in all investigated variables.</
Keywords: Universal prevention program; long-term evaluation

Prevention of familial transmission of depression through a family oriented program targeting parenting as well as the child's social competence - Stemmler, Mark; Kötter, Charlotte; Bühler, Anneke; Jaursch, Stefanie; Beelmann, Andreas; Lösel, Friedrich (Journal of children's services, 2013)
Purpose – The purpose of this article is to evaluate the prevention programme EFFEKT‐E that was designed for preschool children of depressive mothers and contains an intervention for children and for mothers. Design/methodology/approach – Research was carried out in mother‐child clinics in Germany. In total, 220 strained mothers, who were screened for elevated levels of depressive symptoms, were enrolled in the control and 186 in the training group. For evaluation, mothers rated emotional disturbance and social competence of the child as outcome measures before and after the training. Changes in parenting behaviour, perceived parental competence and parenting stress were also assessed. Findings – An effect on emotional disturbance of the child emerged (d=0.52) in the training group. Perceived parental competence increased (d=0.72) and parental stress decreased (d=0.23) significantly under training. EFFEKT‐E has proven to be a valuable programme for preventing depression in offspring of mothers who feel depressed. Originality/value – The article identifies the significance of focusing on parenting as a preventive intervention in the mechanisms of familial transmission of depression and evaluation of a family‐oriented programme for young children designed to achieve this.
Keywords: Mental health; Parents; Children; Depression; Family; Prevention; Maternal depression; Familial transmission; Parenting training; Child training

Prisoners with Islamist relations. What can we learn from their files - King, Sonja; Endres, Johann; Schwaß, Mariann; Stemmler, Mark; Armborst, Andreas; Lauchs, Lora (International Journal of Developmental Science, 2018)

Prognose dissozialen Verhaltens von Kindern: Ergebnisse zur prädiktiven Validität des Cracow Risk Assessment Instruments von Corrado et al. - Wallner, Susanne; Jaursch, Stefanie; Lösel, Friedrich; Stemmler, Mark (45. Kongress der Deutschen Gesellschaft für Psychologie (DGPs), 2006)

Prognose dissozialen Verhaltens von Kindern. Erprobung des Krakau-Instruments von Corrado et al. - Wallner, Susanne; Lösel, Friedrich; Stemmler, Mark; Jaursch, Stefanie (17. Tagung der Fachgruppe Entwicklungspsychologie der Deutschen Gesellschaft für Psychologie (DGPs), 2005)

Propensity, Criminogenic Exposure, and Individual Risk in the Development of Antisocial Behavior in Childhood and Youth: Results from the German CURL-Study - Wallner, Susanne; Stemmler, Mark (Stockholm Criminology Symposium 2016, 2016)

Psychoedukation Angst bei stationären Patienten - Evaluation des kognitiv-verhaltenstherapeutischen Gruppenprogramms „PAsta" - Summ, Elisabeth; Frieling, Helge; Gruß, Barbara; Stemmler, Mark; Bleich, Stefan; Kornhuber, Johannes (Fortschritte der Neurologie - Psychiatrie, 2009)
Hintergrund: Ziel der vorliegenden Studie war es, ein psychoedukatives Gruppenprogramm für stationär behandelte Patienten mit heterogenen Angststörungen zu entwickeln und zu evaluieren. Methode: 28 stationär behandelte Patienten nahmen zusätzlich zur psychiatrischen Standardtherapie an psychoedukativen Gruppensitzungen teil. Die Ergebnisse dieser Gruppe wurden mit 13 Patienten, die nur die Standardtherapie erhielten (Kontrolle) im Prä-Post-Design bezüglich Krankheitswissen, psychischer Gesundheit und Selbstwirksamkeit verglichen. Ergebnisse: Die Psychoedukationsgruppe konnte sich signifikant im Krankheitswissen steigern (d = 0,80). Behandlungseffekte zwischen 0,12 und 0,60 zeigen sich in der psychischen Gesundheit vor allem in der depressiven, aber auch in der Angst-Symptomatik. Erste Ansätze im Aufbau von Selbstwirksamkeit (d = 0,20) sind erkennbar. Schlussfolgerung: Das Hauptziel einer Verbesserung des Krankheitswissens konnte durch das Gruppenprogramm erreicht werden. Insgesamt bestätigen die Studienergebnisse die Bedeutung psychoedukativer Interventionen in der stationären Behandlung schwerstbeeinträchtigter Patienten mit Ängsten.
Keywords: Angststörungen; Psychoedukation; kognitiv-behaviorale Gruppentherapie; Evaluation

Psychological Differences between Radicalized and non-Radicalized Muslim Prisoners: A Qualitative Analysis of their Frame Alignment - Stemmler, Mark; Endres, Johann; King, Sonja; Ritter, Bianca; Becker, Kristina (Monatsschrift für Kriminologie und Strafrechtsreform, 2021)
Do radicalized Muslim prisoners differ from non-radicalized Muslim prisoners with regard to Kruglanski's (2004) quest for significance (QFS), need for (cognitive) closure (NFC), and their frame alignment regarding ideological and religious issues? To answer this research question N = 26 male inmates from Bavarian prisons were interviewed. The radicalized prisoners or extremists (n = 13) had been identified as Salafi or Jihadi adherents by the Bavarian Office for the Protection of the Constitution (Bayerischer Verfassungsschutz) and therefore had a security note. The comparison group were non-radicalized Muslim inmates (n = 13); the vast majority had a migration background.
CRIS-Team WoS Importer:2021-10-22

Quantile regression analysis and other alternatives to ordinary least squares regression: A methodological comparison on corporal punishment - Haupt, Harry; Lösel, Friedrich; Stemmler, Mark (Methodology, 2014)

Quantile Regression-Based Multiple Imputation of Missing Values - An Evaluation and Application to Corporal Punishment Data - Kleinke, Kristian; Fritsch, Markus; Stemmler, Mark; Reinecke, Jost; Lösel, Friedrich (Methodology, 2021)
Quantile regression (QR) is a valuable tool for data analysis and multiple imputation (MI) of missing values - especially when standard parametric modelling assumptions are violated. Yet, Monte Carlo simulations that systematically evaluate QR-based MI in a variety of different practically relevant settings are still scarce. In this paper, we evaluate the method regarding the imputation of ordinal data and compare the results with other standard and robust imputation methods. We then apply QR-based MI to an empirical dataset, where we seek to identify risk factors for corporal punishment of children by their fathers. We compare the modelling results with previously published findings based on complete cases. Our Monte Carlo results highlight the advantages of QR-based MI over fully parametric imputation models: QR-based MI yields unbiased statistical inferences across large parts of the conditional distribution, when parametric modelling assumptions, such as normal and homoscedastic error terms, are violated. Regarding risk factors for corporal punishment, our MI results support previously published findings based on complete cases. Our empirical results indicate that the identified identified "missing at random" processes in the investigated dataset are negligible.
CRIS-Team WoS Importer:2021-10-22

Radicalization potentials of young Muslims in prison: What role do religious factors play? - King, Sonja; Endres, Johann; Stemmler, Mark (Monatsschrift für Kriminologie und Strafrechtsreform, 2021)
How widespread are Islamist attitudes in German prisons? The present research aims at exploring radicalization potentials as well as religion related factors among 87 young Muslim inmates in Bavarian prisons. Participants completed a survey in which we collected measures of religious socialization, religiousness, fundamentalism, and religious militancy. We investigated the distribution of fundamentalist and militant attitudes andcompared the means of Muslims and non-Muslim prisoners (n = 255), calculated regressions, and modelled causal chains linking the relevant concepts through mediation. Our results indicate an increased vulnerability of Muslim inmates for religious radicalization. The results suggest that there is no immediate effect of religious socialization on religious militancy, but that it indirectly influences militant attitudes. The time spent in prison plays a subordinate role. Generalization and implications for the prison context are discussed. 2021 Walter de Gruyter GmbH, Berlin/Boston.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Fundamentalismus; Haft; Militanz; Radikalisierung

Reciprocity and change within the affective family environment in early adolescence - Stemmler, Mark; Petersen, Anne C. (International journal of behavioral development, 1999)
This study examined: (1) the extent and change of affective relationships between young adolescents and their parents over a two-year period; and (2) the amount of reciprocity or concordance of family feelings. Relationship patterns were examined longitudinally from the child's sixth to eighth grade in school. Mothers, fathers, and adolescents completed the Lowman Inventory of Family Feelings (LIFF; J. Lowman, 1974, 1980). The results are based on a longitudinal sample of 54 complete triads and between 128 and 284 dyads depending on measurement point and informant. Family feelings were positive overall, but declined by eighth grade. Here, no differences in results depending on the gender of the adolescent or the parent were detected. Nonreciprocity of family feelings was only present in sixth grade but not in eighth grade. At sixth grade, boys especially, shared less positive family feelings. Results indicate the importance of studying the quality and change of parent–offspring relationships across adolescence.
Keywords: level of family affection & degree of reciprocity of feelings; male vs female 6th–8th grade adolescents; 2 yr study

Resource activation and therapeutic success in in-patient and day-care psychosomatic treatment - Groß, Lisa Johanna; Stemmler, Mark; Erim, Yesim; de Zwaan, Martina (Psychotherapie Psychosomatik Medizinische Psychologie, 2015)
EVALuna:29527

Ressourcenaktivierung in der klinischen Psychologie und Psychotherapie. Überblick über theoretische Hintergründe und aktuelle Forschungsansätze - Groß, Lisa Johanna; Stemmler, Mark; Zwaan, Martina (Fortschritte der Neurologie - Psychiatrie, 2012)
Ziel des vorliegenden Artikels ist es, einen Überblick über theoretische Hintergründe und aktuelle Forschungsansätze der Ressourcenarbeit in der klinischen Psychologie und Psychotherapie zu geben. Ressourcenaktivierung gilt als wichtiger allgemeiner Wirkfaktor der Psychotherapie. Unter Ressourcenaktivierung wird im Allgemeinen ein expliziter Fokus auf die Ressourcen und Potenziale von Klienten verstanden. Nach einer Darstellung der Verwendung des Ressourcenbegriffs werden Überlegungen zur therapeutischen Haltung, Prinzipien der Ressourcenaktivierung, Ansätze zur Ressourcendiagnostik sowie unterschiedliche Forschungsansätze präsentiert. Aktuelle Forschungsarbeiten beschäftigen sich vor allem mit der Erforschung der Zusammenhänge von Ressourcenaktivierung und Prozessvariablen im Rahmen der ambulanten psychotherapeutischen Behandlung.

Risikofaktoren für die Entwicklung dissozialen Verhaltens in der Kindheit und Jugend - Stemmler, Mark; Wallner, Susanne; Link, Eva (Kriminalsoziologie: Handbuch für Wissenschaft und Praxis, 2018)

Schwieriges Temperament im Kindergartenalter, Probleme des Sozialverhaltens und ungünstige elterliche Erziehung - Wallner, Susanne; Beelmann, Andreas; Jaursch, Stefanie; Lösel, Friedrich; Scherer, Stefanie; Stemmler, Mark (16. Tagung der Fachgruppe Entwicklungspsychologie der Deutschen Gesellschaft für Psychologie (DGPs), 2003)

Screening for depression in old age: A comparison of the geriatric depression scale and the depression in old age scale Depressionsscreening im Alter: Ein Vergleich von geriatrischer Depressionsskala (GDS) und Depression im Alter-Skala (DIA-S) - Wunner, Christina; Stemmler, Mark; Masuch, Johanna; Gosch, Markus; Waller, Christiane; Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2021)
Objective: Since 1996, older patients have been treated in the Nuremberg Geriatric Day Hospital. The geriatric depression scale (GDS) is an obligatory part of the geriatric assessment at admission but its use in the clinical setting has revealed some problems. The aim of the study was to compare the GDS with the depression in old age scale (DIA-S) in terms of applicability and psychometric characteristics. Methods: As gold standard a semi-structured interview was used to record the depression criteria according to Diagnostic and Statistical Manual of Mental Disorders (DSM-5). Using a sample of 375 patients, sensitivity and specificity as well as positive and negative predictive values were calculated for both screening tests. Results: No clear superiority of any screening method could be proven. The sensitivity of the DIA‑S in the overall sample was higher than that of the GDS, but the specificity was much lower. In terms of predictive values, there were slight advantages for the GDS. In the sub-samples, poorer values were found in both scales for cognitively impaired or dementia patients with slightly better values for GDS. Conclusion: The DIA‑S can be used very easily in everyday clinical practice, but no advantages of this method compared to GDS could be demonstrated.
CRIS-Team Scopus Importer:2021-08-13
Keywords: Depressive; Major depression; Older adults; Sensitivity; Specificity

Self-reported juvenile delinquency in three surveys over 38 years: A German study on the crime drop - Lösel, Friedrich; Bender, Doris; Sünkel, Zara; Stemmler, Mark (The Psychology of crime, policing and courts, 2016)

Sequentielle strukturierte Risikoprognosen für Dissozialität bei Kindern: Prädiktive Validität des Cracow Instruments für verschiedene Altersphasen - Wallner, Susanne; Lösel, Friedrich; Stemmler, Mark (48. Kongress der Deutschen Gesellschaft für Psychologie (DGPs), 2012)

Sex Differences in Behavior and Behavior Development - Petersen, Anne C.; Stemmler, Mark (The International Encyclopedia of Education (2nd Edition), 1994)

Sex Differences in Behavior and Development - Stemmler, Mark; Petersen, Anne C. (International Encyclopedia of Developmental and Instructional Psychology, 1996)

Skalen zur Messung elterlichen Erziehungsverhaltens bei Vorschul- und Grundschulkindern. Die deutschen Versionen der Parenting Sense of Competence Scale (PSOC) und der Parenting Scale (PARS) - Lösel, Friedrich; Beelmann, Andreas; Jaursch, Stefanie; Scherer, Stefanie; Stemmler, Mark; Wallner, Susanne (2003)

SKT Short Cognitive Performance Test and Activities of Daily Living in Dementia - Lehfeld, Hartmut; Schläfke, Sandra; Hoerr, Robert; Stemmler, Mark (GeroPsych, 2014)
Using data from two randomized, placebo-controlled trials involving 806 outpatients, we performed linear regression analyses to evaluate how cognitive abilities in patients with dementia assessed by the SKT (Syndrom-Kurztest – Short Cognitive Performance Test) correlate with activities of daily living rated by means of the Activities of Daily Living International Scale (ADL-IS). There were significant correlations between SKT total score and ADL-IS total mean score at baseline (r = 0.52, p < .001) as well as between change in SKT total score and change in ADL-IS total mean score during the 24-week treatment period (r = 0.48, p < .001). Significant correlations with ADL-IS total mean scores were also found for both memory and attention/concentration subscores of the SKT.
Keywords: dementia; assessment; cognitive performance; activities of daily living; SKT; ADL-IS

SKT zur Unterscheidung von MCI und Depression - Lehfeld, Hartmut; Stemmler, Mark (NeuroTransmitter, 2020)

Soziale Kompetenz für Kinder und Familien: Ergebnisse der Erlangen-Nürnberger Entwicklungs- und Präventionsstudie - Lösel, Friedrich; Beelmann, Andreas; Jaursch, Stefanie; Stemmler, Mark (2004)

Special Issue on Tree Based Methods for Regression and Classifications – Statistical Methods at the Interface of Graphics and Statistics - Stemmler, Mark; von Eye, Alexander (Pabst Science Publishers, 2019)
The editors of this Special Issue invited scholars to contribute new formal and statistical developments as well as interesting applications in the field of tree-based methods in psychological research. Among the many interesting properties of tree-based methods is that they enable researchers to investigate effects of multiple independent variables on one or several dependent variables without any restriction on level of measurement. The contributions included in this issue contain theoretical considerations, new methods for tree-based analysis, simulation studies, and sample analyses of interesting psychological data sets. Also included are software developments and applications (R packages such as confreq, rpart, dHISC and partykit). The reader will find articles that encompass classification and regression tree methods (CART), CHAID, and bootstrap regression tree methods. This special issue first presents a selection of new developments and theoretical contributions, and, second, a selection of applications of tree-based methods. Section I: Theory and Methods In the first manuscript of the theory and methods section, Michael P. van Wie, Xintong Li, and Wolfgang Wiedermann propose and discuss methods for the Identification of Confounded Subgroups Using Linear Model-Based Recursive Partitioning. The authors aim at detecting confounded subgroups in linear regression models by way of combining a confounder detection approach, based on kernel-based independence testing, with model-based recursive partitioning. The second article, contributed by Markus Fritsch, Harry Haupt, Friedrich Lösel, and Mark Stemmler, discusses Data science alternatives to ordinary least squares: Investigating the risk factors for corporal punishment with decision trees and random forests. The authors demonstrate that decision trees and random forests enable data-driven modeling. These methods are valuable tools in psychological research to gain new insights and to validate existing results. In an application, Fritsch and colleagues examine the behavior of father’s aggressiveness, dysfunctional parent-child interactions, and other risk factors for corporal punishment of children by their fathers. This article is followed by Analyzing Tree Structures with Configural Frequency Analysis and the R-package confreq by Mark Stemmler, Jörg Henrik-Heine and Susanne Wallner. This article describes the use of Configural Frequency Analysis (CFA) for detecting a tree structure in data that was analyzed with the SPSS module Answer Tree. In addition, the application of the R package confreq is demonstrated. The data example is taken from a longitudinal study on deviant and delinquent behavior in juveniles. In the last article of the theory and methods section, it is entitled Log-linear and Configural Analysis of Tree Structures, Alexander von Eye, Wolfgang Wiedermann and Stefan von Weber propose two methods for the analysis of existing tree structures. These methods are log-linear modeling and Configural Frequency Analysis (CFA). In a data example, students’ decisions and life satisfaction are examined. Section II: Applications The first article of the application section is contributed by Cody Ding and Yuyang Zhao. The authors present on Using Tree-Based Regression to Examine Factors Related to Math Ability Among 15-Year Old Students to predict students’ mathematics ability, particularly subgroups of students who share characteristics that are associated with different levels of math ability. Based on PISA 2012 data from the United States and China, the authors used regression tree analysis to select the most salient predictors of math ability, and identify subgroups of 15-year-old students who were likely to be proficient in math ability. The second article of the application section, co-authored by Eun-Young Mun and Feng Geng is entitled Predicting Post-experiment Fatigue among Healthy Young Adults: Random Forest Regression Analysis. In this paper, a random forest regression analysis is used to predict post-experiment fatigue in a sample of 212 participants between the ages of 18 and 30 following a mildly stressful experiment. The random forest regression analysis is used together with a built-in cross-validation function. We hope that the readers will enjoy this Special Issu
Keywords: Tree-based regression

The Alzheimer’s Disease Activities of Daily Living International Scale (ADL-IS) - Reisberg, Barry; Finkel, Sanford; Overall, John; Schmidt-Gollas, Norbert; Kanowski, Siegfried; Lehfeld, Hartmut; Hulla, Franz; Sclan, Steven G.; Wilms, Hans-Ulrich; Heininger, Kurt; Hindmarch, Ian; Stemmler, Mark; et al. (International Psychogeriatrics, 2001)
Background: Activities of daily living (ADL) deficits are integral components of dementia disorders, and ADL measures are among the most robust markers of the course of Alzheimer's disease (AD). Despite this acknowledged importance, no clearly useful ADL instrument for cross-cultural application in pharmacologic trials in the early stages of AD had been available. Method: An international effort was launched to develop an ADL scale for pharmacologic trials in early AD. Steps taken from 1990 to the present included: (1) international scientific working group meetings and reviews, (2) reviews of existing measures, (3) collating of existent, nonredundant items, (4) querying experts for new items, (5) interviews with informants and subjects in the USA, France, and Germany, toward the identification of potential new items, (6) identification of an item pool based upon these procedures, (7) creation of a trial instrument, (8) piloting of this instrument, and (9) refinement of the scale based upon statistical analysis of the pilot data. Final item selection was based upon: (1) relevance for [greater-than-or-equal] 80% of subjects in severity-stratified USA and German samples; (2) absence of gender and national biases; (3) significant (p < .05) discrimination between (a) normal versus mildly impaired and (b) mildly impaired versus moderately to moderately severely impaired subjects; and (4) Global Deterioration Scale (GDS) scores accounting for [greater-than-or-equal] 12% of variance in the item after controlling for age and gender. Results: An ADL scale consisting of 40 items that correlate with the global and cognitive progress of AD is developed for international usage in pharmacologic trials in incipient, mild, moderate, and moderately severe AD. The scale contains 40 items falling within 13 ADL categories. The 40-item scale is shown to have .81 correlation with GDS staging,.81 with mental status assessment (Mini-Mental State Examination), and .81 with a psychometric test (the SKT) (p values < .001). Conclusion: This scale can be used to measure therapeutic response in AD.

The Application of Psychological Assessment Methods in Sport Psychology in Germany - Ziemainz, Heiko; Neumann, Gabriele; Rasche, Friederike; Gelius, Peter; Stemmler, Mark (Sport science review, 2009)

The Application of the SKT Short Cognitive Performance Test to English-Speaking Populations - Stemmler, Mark; Schneider, Sophia; Poon, Leonard (Psych, 2021)
The SKT (Syndrom-Kurz-Test) is a well-established short cognitive performance test for the detection of attention and memory deficits in Germany. The goal of this paper is to test whether the SKT could be applied to English-speaking populations to screen cognitive impairments in the US, Australia, and Ireland. A regression-based continuous norming technique was applied. Standardized test results obtained from German-speaking (n = 1056) and English-speaking (n = 285) samples were compared. Both samples consisted of cognitively unimpaired, community-dwelling, and independently living volunteers (non-patients) over 60 years of age. Means, medians, and standard deviations of raw scores were calculated. A high similarity in the raw value distributions of the criterion variables and a comparison of German and English multiple regression residuals indicated the equivalence among the samples. In addition, the obtained multiple regression equations for predicting the subtest scores including the explained variances (R2) were highly comparable. Age and intelligence turned out to be the most important and necessary predictors for each subtest performance. The results suggest that the new regression-based norming of the SKT can be validly used in the three English-speaking countries.
Keywords: neuropsychology; culture fair test; regression-based continuous norming; processing speed

The association between prenatal alcohol consumption and preschool child stress system disturbance - Grimm, Jennifer; Stemmler, Mark; Golub, Yulia; Schwenke, Eva; Goecke, Tamme W.; Fasching, Peter; Beckmann, Matthias; Kratz, Oliver; Moll, Gunther; Kornhuber, Johannes; Eichler, Anna (Developmental Psychobiology, 2021)
Background: Drinking alcohol during pregnancy is considered a risk factor for child development; however, child biomarkers of prenatal alcohol exposure have been rarely studied. We examined whether a meconium alcohol metabolite (ethyl glucuronide, EtG) was associated with child cortisol concentrations at primary school age. Methods: For 137 children, prenatal alcohol exposure was operationalized by the meconium biomarker EtG and by maternal self-reports during pregnancy. Two EtG cut-offs (EtG ≥10 ng/g and EtG ≥112 ng/g) were applied. Cortisol concentrations were measured in saliva and hair samples. Results: Children with EtG ≥10 ng/g showed significantly reduced hair cortisol concentrations (HCCs) (p =.050, (Formula presented.) = 0.042). For children with EtG ≥112 ng/g, the cortisol awakening response (CAR) was significantly decreased (p =.025, (Formula presented.) = 0.070). These effects were also present in correlational analyses with continuous EtG data, speaking for partly dose-dependent effects. Especially, within the EtG ≥112 ng/g group, the basal (CAR: rp = −.642, p =.120) and cumulative (HCC: rp = −.660, p =.107) cortisol parameters were associated with child emotional symptoms at medium effect size. Conclusions: The present study showed both the biological association of intrauterine alcohol exposure with the cortisol stress system, partly dose-dependent, and the functional association with emotional and behavioral symptoms.
CRIS-Team Scopus Importer:2020-10-16
Keywords: alcohol; biomarker; child; cortisol stress system; ethyl glucuronide; hypothalamus-pituitary-adrenal axis; intrauterine alcohol exposure; meconium; pregnancy

The Contributions of Propensity, Delinquent Peers, Low Parental Supervision, and Empathy to the Emergence of Antisociality in Childhood and Youth: Testing Developmental Path Models Combining Psychological- and Sociological-Criminological Approaches - Wallner, Susanne; Stemmler, Mark; Reinecke, Jost (International Journal of Developmental Science, 2020)

The Development of Deviant and Delinquent Behavior over the Life Course in the Context of Processes of Social Inequalities - Reinecke, Jost; Stemmler, Mark; Sünkel, Zara; Schepers, Deborah; Weiss, Maren; Arnis, Maria; Meinert, Julia; Uysal, Burcu; Pöge, Andreas; Wallner, Susanne; Wittenberg, Jochen (2013)

The Development of Deviant and Delinquent Behavior over the Life Course: The Study „Chances and Risks in the Life Course“ at a Glance - Wallner, Susanne; Stemmler, Mark (International Conference on Psychology and Law - "EAPL & World 2015", 2015)

The Erlangen test of activities of daily living in persons with mild dementia or mild cognitive impairment (ETAM) - an extended validation - Book, Stephanie; Luttenberger, Katharina; Stemmler, Mark; Meyer, Sebastian; Grässel, Elmar (BMC Psychiatry, 2018)
BACKGROUND: The ability to perform activities of daily living (ADLs) is a central marker in the diagnosis and progression of the dementia syndrome. ADLs can be identified as basic ADLs (BADLs), which are fairly easy to perform, or instrumental ADLs (IADLs), which involve more complex activities. Presently, the only performance-based assessment of IADL capabilities in persons with cognitive impairment is the Erlangen Test of Activities of Daily Living in Persons with Mild Dementia or Mild Cognitive Impairment (ETAM). The aim of the present study was to revalidate the ETAM in persons with mild cognitive impairment (MCI) or mild dementia and to analyze its application to persons with moderate dementia. METHODS: We used baseline data from a cluster randomized controlled trial involving a sample of 443 users of 34 day-care centers in Germany. We analyzed groups of persons with MCI, mild dementia, and moderate dementia, categorized on the basis of the Mini-Mental State Examination (MMSE) and the Montreal Cognitive Assessment (MoCA). An item analysis was performed, and new discriminant validities were calculated. We computed a confirmatory factor analysis (CFA) to examine the postulated theoretical model of the ETAM with all six items loading on a single IADL factor. This was the first time that the ETAM's sensitivity to change was analyzed after a time period of 6 months. RESULTS: The overall sample scored on average 17.3 points (SD = 7.2) on the ETAM (range: 0-30 points). Persons with MCI scored on average 23.2 points, persons with mild dementia scored 18.4 points, and persons with moderate dementia scored 12.9 points, p < .001 (ANOVA). The item analysis yielded good difficulty indices and discrimination powers. The CFA indicated a good fit between the model and the observed data. After 6 months, both the ETAM score at baseline and the change in MMSE score (t0-t1) were significant predictors of the ETAM score at t1. CONCLUSIONS: The ETAM is a valid and reliable instrument for assessing IADL capabilities in persons with MCI or mild dementia. It is sensitive to changes in cognitive abilities. The test parameters confirm its application to persons with moderate dementia. TRIAL REGISTRATION: Identifier: ISRCTN16412551 (Registration date: 30 July 2014, registered retrospectively).
EVALuna2:35661

The Etiology of Adolescent Depression: Differences by Severity, Gender, and Developmental Stage - Stemmler, Mark (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1993)

The gender-differential significance of work and family: An exploration of adolescent experience and expectation - Camarena, Phame; Stemmler, Mark; Petersen, Anne C. (Adolescence in Context: The Interplay of Family, School, Peers, and Work in Adjustment, 1994)

The Importance of Propensity, Criminogenic Exposure, and Individual Risk in the Development of Antisociality: Findings from the CURL-Study - Wallner, Susanne; Stemmler, Mark (16th Annual Conference of the European Society of Criminology, 2016)

The Median Quartiles Test Revisited - von Eye, Alexander; Neubauer, Aljoscha; Stemmler, Mark (Studia Psychologica, 1996)
Describes R. K. Bauer's (1962) Median Quartiles Test, a strategy for simultaneously testing for homeopoetic and heteropoetic treatment effects in a 2-group experimental design. The strategy is based on H. O. Lancaster's (1949) chi-square partition of a 4 * 2 table with a dependent variable that has 4 ordinal categories. The test is reformulated to be suitable for assessing differences in location and orthogonal decomposition is introduced for detecting differences in locations and dispersion. One specific characteristic of the reformulated Bauer median quartiles test is that it does not need alignments in location for efficient detection of differences in location. Examples from drug research illustrate the use of the reformulated test.
Keywords: Nonparametric Statistical Tests; Treatment

The newly normed SKT reveals differences in neuropsychological profiles of patients with MCI, mild dementia and depression - Lehfeld, Hartmut; Stemmler, Mark (Diagnostics, 2019)
The SKT (Syndrom-Kurztest) is a short cognitive performance test assessing deficits of memory and attention in the sense of speed of information processing. The new standardization of the SKT (2015) aimed at improving its sensitivity for early cognitive decline due to dementia in subjects aged 60 or older. The goal of this article is to demonstrate how the neuropsychological test profile of the SKT can be used to provide valuable information for a differential diagnosis between MCI (mild cognitive impairment), dementia and depression. n = 549 patients attending a memory clinic (Nuremberg, Germany) were diagnosed according to ICD-10 and tested with the SKT. The SKT consists of nine subtests, three for the assessment of memory and six for measuring attention in the sense of speed of information processing. The result of the SKT test procedure is a total score, which indicates the severity of overall cognitive impairment. Besides the summary score, two subscores for memory and attention can be interpreted. Using the level of depression as a covariate, statistical comparisons of SKT test profiles between the three patient groups revealed that depressed patients showed more pronounced deficits than MCI patients in all six attention subtests. On the other hand, MCI patients displayed significantly greater mnestic impairment than the depressed group, which was indicated by significant differences in the memory subscore. MCI and dementia patients showed similar deficit patterns dominated by impairment of memory (delayed recall) with MCI patients demonstrating less overall impairment. In sum, the SKT neuropsychological test profiles provided indicators for a differential diagnosis between MCI and beginning dementia vs. depression.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Cognitive assessment; Dementia; Depression in old age; Differential diagnosis depression vs. MCI/dementia; Mild cognitive impairment; SKT (Syndrom-Kurztest)

The role of participants’ self-selected future smoking goals in adolescent smoking cessation interventions - Thrul, Johannes Erich; Stemmler, Mark; Bühler, Anneke; Goecke, Michaela (Drug and Alcohol Dependence, 2014)
BACKGROUND: There is an implicit assumption that abstinence is the treatment goal of young smokers that deliberately participate in cessation interventions, but this may not always be the case. To gain information on subgroups of adolescent intervention participants, we compare participants who want to achieve smoking abstinence (Abst) with those stating a non-abstinence future smoking goal (NAbst), with regard to baseline characteristics, reasons for participation, quit motivation, retention, goal attainment, and smoking abstinence. METHODS: The sample consisted of 202 adolescent smokers (49.5% female). At baseline, 118 (58.4%) indicated abstinence as future smoking goal and 84 (41.6%) indicated non-abstinence. All participants received a behavioral smoking cessation intervention. Assessments took place before, during, and after treatment, and at 6-month follow-up. Regression analyses were conducted. RESULTS: Abst and NAbst participants reported similar baseline characteristics. Abst participants, however, were more likely to report a previous quit attempt and indicated a higher quit motivation before and during treatment. Abst participants were more likely to participate based on own initiative and NAbst participants because of participating friends. Both groups attended a similar number of intervention sessions and were equally likely to attain their self-selected smoking goal. However, more Abst participants reported a successful quit attempt during treatment and abstinence at post-treatment and follow-up. CONCLUSIONS: NAbst participants may represent a substantial subgroup in smoking cessation interventions for adolescents. Results indicate that future smoking goals can influence treatment outcomes. NAbst participants in treatment may benefit from additional information on the negative health consequences of light smoking.

The stability of externalizing behavior in boys from preschool age to adolescence: A person-oriented analysis - Stemmler, Mark; Lösel, Friedrich (Psychological Test and Assessment Modeling, 2012)

The Usefulness of the Regression-Based Normed SKT Short Cognitive Performance Test in Detecting Cognitive Impairment in a Community Sample - Stemmler, Mark; Arnold, Melina; Numbers, Katya; Kochan, Nicole A.; Sachdev, Perminder S.; Brodaty, Henry (Diagnostics, 2024)
Background: The SKT is a short cognitive performance test designed to assess impairments in memory and cognitive abilities such as attention and speed of information processing. In 2019, new regression-based norms for the English version of the SKT were calculated. This study has two aims: to establish valid cut-offs for distinguishing between no cognitive impairment, mild cognitive impairment (MCI), and dementia (1) and to cross-validate the new norms for detecting MCI and dementia in a community sample of older adults with clinical diagnoses (2). Methods: The validation sample included 143 older adults (mean age = 87.7, SD = 3.55) from the Sydney Memory and Aging Study (MAS Study). Participants were classified as having normal cognition, MCI, or dementia solely based on a consensus diagnosis; in addition, three tests (SKT, Mini-Mental State Examination (MMSE), and Addenbrooke’s Cognitive Examination III (ACE-III)) to measure cognitive impairment were applied. Sensitivity and specificity for all three tests, as well as bivariate correlations, were calculated. Results: The sensitivity of the SKT for the differentiation of cognitive impairment (MCI or dementia) from normal cognition was 80.6%. The convergence between the SKT and the consensus diagnoses was 70.3% for all three diagnostic groups. All correlations between the three tests and the consensus diagnosis were significant (p < 0.01). Conclusions: In sum, it can be stated that the SKT is a valid tool for detecting early stages of cognitive impairment, performing very well in discriminating between no cognitive impairment and cognitive impairment (MCI or dementia).
CRIS-Team Scopus Importer:2024-10-25
Keywords: cognitive assessment; dementia; MCI; regressions-based norming; sensitivity; short cognitive performance test (SKT); specificity; Sydney Memory and Aging Study (MAS)

The use of clinical experience to stage the severity of functional impairments in Alzheimer's disease - Finkel, Sanford; Bergener, Manfred; Hulla, Franz; Stemmler, Mark; Overall, John (Human Psychopharmacology-Clinical and Experimental, 1996)
Examined international consistency and elucidated internationally-based clinical understanding of the chronology of increasing functional impairment in Alzheimer's disease (AD). 28 experienced clinicians from Germany and the US rated the stage of AD at which each of the 44 manifestations of cognitive, behavioral, or functional impairment is most clinically relevant. Data were subjected to 3 methods of metric scale analysis: equal appearing intervals, principal components, and paired comparison scaling. Finally, a single average T-score value for each item was calculated, and the 44 items were listed in rank order according to their average severity scale values. The resulting ordering and associated scale values provided a consistent and reliable description of the course of functional impairments in AD as seen by experienced clinicians in the 2 countries.
Keywords: Alzheimer's Disease; Clinical Judgment (Not Diagnosis); Cognitive Ability; Disease Course; Severity (Disorders); Clinicians

The validity of the Cracow Instrument in the prediction of antisocial development in preschool children: A five-year longitudinal community based study - Wallner, Susanne; Lösel, Friedrich; Stemmler, Mark; Corrado, Ray (International Journal of Forensic Mental Health, 2018)

Training im Problemlösen (TIP): Ein sozial-kognitives Kompetenztraining für Kinder im Grundschulalter - Stemmler, Mark (Kinder(-nöte) im Blick – Kinder schützen, Gefährdungen und Risiken vorbeugen, 2008)

TUIM® urofemin – Ein Nahrungsergänzungsmittel zur Erhaltung der Blasengesundheit bei Frauen: Evaluation einer Verzehrbeobachtung - Stemmler, Mark; Warbruck, Ingo (Klinische Forschung und Recht, 2006)

[U25] – Online-Suizidpräventions-Beratung. Erste Ergebnisse zu Implementation und Evaluation - Weiss, Maren; Hildebrand, Anja; Braun-Scharm, Hellmuth; Stemmler, Mark (Kinder- und Jugendschutz in Wissenschaft und Praxis, 2020)

Universal prevention of antisocial development: Short- and long-term effects of a child- and parent-oriented program - Lösel, Friedrich; Stemmler, Mark; Jaursch, Stefanie; Beelmann, Andreas (Monatsschrift für Kriminologie und Strafrechtsreform, 2009)

Using Configural Frequency Analysis as a Person-Centered Analytic Approach with Categorical Data - Stemmler, Mark; Heine, Jörg-Henrik (International journal of behavioral development, 2016)

Validation of Chinese Version of SKT (Syndrom Kurztest): A Short Cognitive Performance Test for the Assessment of Memory and Attention - Lu, Yao; Hu, Jingchao; Stemmler, Mark; Guo, Qihao (Diagnostics, 2021)

Werden suizidgefährdete junge Menschen durch Online-Beratung erreicht? - Weiss, Maren; Hildebrand, Anja; Braun-Scharm, Hellmuth; Weckwerth, Klaus; Held, Dagmar; Stemmler, Mark (Zeitschrift für Kinder- und Jugendpsychiatrie und Psychotherapie, 2020)

Why Do Students Become Cyberbullies? Elucidating the Contributions of Specific Developmental Risks to Cyberbullying - Wallner, Susanne; Stemmler, Mark (Psych, 2021)
Cyberbullying is currently considered as a widespread problem among children and adolescents; in particular, the risks of cyberbullying have recently been examined. The empirical analyses of the present work are based on data from a German longitudinal study. The self-reports of adolescents from Dortmund and Nuremberg on both cyberbullying and individual and contextual characteristics were taken into account. The two-wave panel encompasses N = 871 adolescents (44.5% male); the average age was M = 15.1 years (SD = 0.83) at t1. Data on cyberbullying refer to sending insults or threats to others via the Internet, spreading rumours or talking badly about others via the Internet, and sending private e-mails, photos or similar from others in order to embarrass or ridicule the persons concerned. Other characteristics relate to single aspects of psychopathy (egocentric egotism, low self-control, empathy deficits), acceptance of violence, and delinquent peers. The path analytical findings illustrate the predictive relationships between both individual and contextual risks and cyberbullying in adolescence. The empirical results are discussed, among others, from the perspective of developmental and life-course criminology.
Keywords: cyberbullying; risk; psychopathic traits; longitudinal study; school-based survey

Wirken Online-Peer-Suizidpräventionsprogramme? - Hildebrand, Anja; Weiss, Maren; Braun-Scharm, Hellmuth; Stemmler, Mark (Zeitschrift für Klinische Psychologie und Psychotherapie, 2022)
Zusammenfassung.Theoretischer Hintergrund. Suizid ist weltweit die zweithäufigste Todesursache bei jungen Menschen. Es scheint sinnvoll, speziell auf diese Zielgruppe zugeschnittene Angebote anzubieten. Fragestellung. Ziel dieser Untersuchung ist, den von den Nutzenden wahrgenommenen Beratungserfolg eines Online-Peer-Suizidpräventionsprogramms zu ermitteln und zu prüfen, welche Merkmale mit dem Beratungserfolg zusammenhängen. Methode. Daten eines Online-Fragebogens wurden ausgewertet (N = 318). Ergebnisse. Bei zwei Drittel der Befragten verminderte sich die Suizidalität. Wichtige Variablen zur Vorhersage der Veränderung der Suizidalität waren der Eindruck der Ratsuchenden, dass die Peers die persönlichen Anliegen verstehen und die Anregung zu einer Verhaltensänderung. Das Peerverhalten trug signifikant zur Vorhersage der subjektiven Nützlichkeit und der allgemeinen Situation bei. Schlussfolgerungen. Die Studie liefert positive Ergebnisse hinsichtlich der Evaluierung der Online-Suizidpräventions-Beratung. Da das Verstanden fühlen und das Peerverhalten im Zusammenhang mit dem Beratungserfolg steht, könnte der Peer-Ansatz und die damit einhergehende positive Beziehungserfahrung wichtig sein. Do Online Peer Suicide Prevention Programs Work? A Study of the Success of Counseling and Its Predictors Abstract.Background. Suicide is the second leading cause of death among young people worldwide. It, therefore, makes sense to offer services tailored specifically to this target group. Objective. This study serves to determine the success of an online peer suicide prevention counseling perceived by users, and to examine the characteristics related to the success of such counseling. Methods. We evaluated data from an online questionnaire (N = 318). Results. Suicidality decreased in two-thirds of the respondents. Important variables were the impression of those seeking advice that their peers understood their concerns, and that they were encouraged to change their behavior. Peer behavior contributed significantly to predicting the subjective usefulness and the general situation. Conclusions. The study provides positive results regarding the evaluation of [U25] online suicide prevention counseling. Since the feeling of being understood and peer behavior are related to counseling success, the peer approach and the positive relational experience that accompanies it could be valuable.

Wirkung sportlicher Aktivität auf das aktuelle Befinden von Menschen mit Asthma bronchiale – Verlaufsanalysen in der Bewegungstherapie im Rahmen der pneumologischen Rehabilitation - Geidl, Wolfgang; Maul, Sabrina; Lehbert, N.; Wingart, S; Stemmler, Mark; Schultz, K.; Pfeifer, Klaus (Pneumologie, 2016)

Women-only versus mixed-gender groups in multimodal, day clinic treatment of trauma-related disorders - Philipps, Anke; Hepp, Tobias; Silbermann, Andrea; Morawa, Eva; Stemmler, Mark; Erim, Yesim (Zeitschrift für Psychosomatische Medizin und Psychotherapie, 2022)
Background: In the German healthcare system benefits include inpatient and day clinic psychotherapy of trauma-related disorders, which are often provided in gender specific groups. Despite this widespread practice, the actual impact and potential outcome have been studied relatively scarcely and are still open to debate. The present study therefore examines whether the therapeutic relationships in the group vary depending on the group composition and whether this has an effect on therapy outcome. Methods: 66 patients (N = 55 women) were treated in our multimodal, day clinic groupbased treatment program and filled out symptom questionnaires (ETI, BDI-II, PHQ-15, Questionnaire on social support) at admission and discharge and the Group Questionnaire (GQ; including subscales positive bonding, positive working and negative relationships) at the end of each of the eight weeks of treatment. Patients took part in five women-only and six mixed-gender groups and underwent therapy in a closed group format, so that they began and ended therapy within the same group. All patients were diagnosed with trauma-related disorders, which included PTSD, cPTSD, depression, somatoform disorders and further mental diseases. Outcome data were examined using functional regression analysis and linear mixed models. Results: In women-only groups, positive bonding and positive working relationship were significantly higher than in mixed-gender groups. Negative relationship ratings were significantly lower in women-only groups, especially in the middle phase of treatment. However, no effect of an exclusively female group composition on treatment outcome was found, except for the higher increase of perceived social support for patients treated in women-only groups. Conclusions: Group relationships were considered more pleasant in women-only groups than in mixed-gender groups, but this had no effect on the symptom-based therapy outcome. To enhance feelings of safety and comfort, traumatized women should have the possibility to choose whether to be treated in a women-only or a mixed-gender group.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Day Clinic; Group Relationships; PTSD; Trauma; Women-Only Groups

Zur Wirksamkeit von Brainspotting - Ein neues Therapieverfahren zur Behandlung von Posttraumatischen Belastungsstörungen - Hildebrand, Anja; Grand, David; Stemmler, Mark (Trauma - Zeitschrift für Psychotraumatologie und ihre Anwendungen, 2015)
In einer Vorstudie wurde die Wirksamkeit des von David Grand neu entwickelten Therapieansatzes „Brainspotting“ für die Behandlung von Posttraumatischen Belastungsstörungen (PTBS) bewertet. Es wurden Daten von 22 Klienten aus Deutschland und den USA ausgewertet, die mit Brainspotting behandelt wurden. Nach Einschätzung der Therapeuten war bei einem Großteil der Klienten eine Verbesserung der Symptomatik ersichtlich. Laut Selbstbericht der Klienten nahm die emotionale Belastung durch negative traumabezogene Kognitionen ab. Diese ersten Ergebnisse zeigen, dass mit Brainspotting die Behandlung von PTBS um eine effektive Methode erweitert werden könnte.
Keywords: Brainspotting; Trauma; Therapie; Wirksamkeitsstudie; Vorstudie

Zusammenhänge zwischen den kognitiven Leistungen in einem Demenzscreening (SKT) und im einem Intelligenztest (WAIS-IV) bei älteren Menschen: Welche kognitiven Leistungseinbußen im Alter sprechen für einen möglichen pathologischen Abbauprozess? - Pauli, Laura; Daseking, Monika; Petermann, Franz; Stemmler, Mark (Zeitschrift für Gerontologie und Geriatrie, 2018)